Printed matter
The printed matter with a resin base and release primer layer using polyethyleneimine or polybutadiene compounds effectively bonds and detaches the printing layer from the base material, solving bonding and separation challenges in packaging materials.
Patent Information
- Application Number
- JP2023113034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Existing packaging materials face challenges in reliably bonding the base material with the printed layer and efficiently separating the printed layer from the base material after use, particularly due to insufficient lamination suitability and residual adhesive issues.
A printed matter is developed with a resin base material, a release primer layer formed using a desorption primer composition containing polyethyleneimine or polybutadiene compounds, and a printing layer formed with inkjet or offset ink compositions, allowing for reliable bonding during use and easy detachment post-use.
The solution enables reliable bonding of the base material and printing layer during use and facilitates easy separation of the printed layer from the substrate, addressing the issues of insufficient lamination suitability and residual adhesive.
Smart Images

Figure 2025010808000001 
Figure 2025010808000002 
Figure 2025010808000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to printed matter. [Background technology]
[0002] Packaging materials made from various plastic films are used for food, confectionery, household goods, pet food, etc., from the viewpoints of design, economy, content protection, transportability, etc. Furthermore, gravure printing or flexographic printing is applied to many packaging materials with the intention of adding designs and messages that will appeal to consumers. To obtain these packaging materials, printing is performed by printing directly onto the surface of the base film of the packaging material, or by applying an adhesive or anchor agent to the printed surface of the base film of the packaging material as needed, and then laminating the film. In printing for laminating films, a colored ink composition and a white ink composition are printed in sequence on various films such as polyester, nylon, and aluminum foil, and then a polyethylene film or polypropylene film for heat sealing is laminated on the printed layer of the white ink composition by dry lamination using an adhesive or extrusion lamination using an anchor coating agent (see Patent Document 1).
[0003] In recent years, packaging, plastic bottles, and other plastic products made from plastic film have been discarded and dumped into the ocean as litter, causing environmental pollution problems. These plastic products break down in seawater, turning into submicron-sized fragments (microplastics), which float in the water. When these plastics are ingested by marine organisms such as fish, they become concentrated in their bodies. This raises concerns about the health of seabirds and humans who consume these marine organisms as food.
[0004] As one of various efforts to reduce microplastics in order to alleviate such problems, a recycling method has been proposed in which the plastic substrate of a laminate is removed from a laminate to which a printing ink composition has been laminated. As methods for removing the plastic substrate of a laminate, a removing ink composition (see, for example, Patent Document 2), a removing adhesive (see, for example, Patent Document 3), a removing anchor coating agent, etc. (see, for example, Patent Documents 4 to 6), and a removing liquid (see, for example, Patent Document 7) have been proposed. However, in these methods, the use of hot water as a release liquid is not sufficient for desorption, and when used in a laminate printing ink composition, there is a problem in that the lamination suitability is insufficient. In addition, there are also printed materials in which printing is performed on the paper substrate side of laminated paper, which is made by applying an adhesive to a base film and bonding a paper substrate to it, but this has the problem that the adhesive remains on the base film even after the paper substrate is removed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-97959 [Patent Document 2] Patent No. 6631964 [Patent Document 3] Patent No. 6642688 [Patent Document 4] Patent No. 6388131 [Patent Document 5] Japanese Patent Publication No. 2020-175620 [Patent Document 6] International Publication No. 2021 / 090690 [Patent Document 7] Patent No. 6690806 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to reliably bond a substrate and a printed layer during use, and to more easily separate the printed layer from the substrate after use and subsequently separate the printed layer from a release liquid. Another objective of the present invention is to easily separate and separate the adhesive layer from the printed matter when a paper substrate is laminated to a substrate film via an adhesive layer. [Means for solving the problem]
[0007] The present inventors have found that the above problems can be solved by producing the following printed matter, and have come up with the present invention. 1. A printed matter in which a resin substrate, a detachable primer layer, and a printing layer are formed in this order, wherein the printing layer is formed from an inkjet ink composition and / or an offset ink composition, and the detachable primer composition used to form the detachable primer layer contains a polyethyleneimine-based compound and / or a polybutadiene-based compound having an amine value of 5.0 to 25.0 mmol / g. 2. A printed matter formed in the following order: a resin substrate, a detachable primer layer, an adhesive layer, a paper substrate layer, and a printing layer, wherein the printing layer is formed from an inkjet ink composition or an offset ink composition, and the detachable primer composition used to form the detachable primer layer contains a polyethyleneimine-based compound and / or a polybutadiene-based compound having an amine value of 5.0 to 25.0 mmol / g. 3. The printed matter according to 1 or 2, wherein the detachment primer composition containing a polyethyleneimine-based compound having an amine value of 5.0 to 25.0 mmol / g contains at least one of the following A to C: A. Polyethyleneimine Compounds B. A mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent C. Siloxane-modified polyethyleneimine compounds 4. The printed matter according to 3, wherein the polyethyleneimine compound or siloxane-modified polyethyleneimine compound has a number average molecular weight of 1,000 to 200,000. 5. The printed matter according to 3, wherein the polyethyleneimine compound or siloxane-modified polyethyleneimine compound has a mass average molecular weight of 4,000 to 800,000. 6. The printed matter according to any one of 1 to 5, wherein the polybutadiene compound-containing detachment primer composition contains a hydroxyl group-containing polybutadiene compound and / or a carboxyl group-containing polybutadiene compound. 7. The printed matter according to any one of 1 to 6, wherein a layer made of a varnish composition is formed on the printed layer. [Effects of the Invention]
[0008] According to the present invention, the substrate and the printing layer can be reliably bonded together during use, and after use, The printed layer can be more easily separated from the substrate, and then the printed layer can be detached from the substrate in a detachment step, and the printed layer can be easily separated from the detachment liquid. Furthermore, according to the present invention, it is possible to more easily separate and detach the adhesive layer from the substrate film of a printed matter in which a paper substrate is laminated to the substrate film via the adhesive layer. DETAILED DESCRIPTION OF THE INVENTION
[0009] The present invention is based on the following points and can be used for various printing methods and printed materials for various purposes. In this specification, the detachable primer composition of the present invention may sometimes be referred to simply as a "primer composition," the layer formed from the detachable primer composition may sometimes be referred to simply as a "detachable primer layer," and the resin substrate of the present invention may sometimes be referred to simply as a "substrate." The present invention is significant in that it employs a specific composition as the release primer layer.
[0010] [Structure of printed matter] The printed matter of the present invention is a printed matter in which a resin substrate, a detachable primer layer, and a printing layer are formed in this order, or a printed matter in which a resin substrate, a detachable primer layer, an adhesive layer, a paper substrate layer, and a printing layer are formed in this order. The resin substrate is as follows, and the detachable primer layer and the printed layer are layers formed from the detachable primer composition and the printing ink composition, respectively. The adhesive and paper substrate for forming the adhesive layer are not particularly limited, and any known adhesive may be used as long as the adhesive can adhere to the detachable primer layer with sufficient adhesive strength, the paper substrate can be adhered to by the adhesive with sufficient strength, and any desired printed layer can be formed thereon.
[0011] [Removal primer composition] The detachment primer composition of the present invention is a composition for forming a detachment primer layer that is provided so as to be positioned between the surface of a resin substrate and a printed layer or an adhesive layer. When recycling a printed material after use, the detachment primer composition is used to separate a resin film or the like that serves as the substrate for the printed material from the printed layer or adhesive layer formed thereon, thereby detaching the substrate from the printed material. The detachment primer composition may be either an aqueous or oil-based composition. The primer composition used in the present invention is a detachable primer composition, and differs in its use and required properties from an anchor coating agent used, for example, when an anchor coating layer is further formed on a printed surface formed on a substrate and a resin film or the like is laminated thereon. The primer composition used in the present invention is also a composition for forming a primer layer on a resin substrate before printing the printing ink composition on the resin substrate. As the detachment primer composition, a polyethyleneimine-based compound and / or a polybutadiene-based compound having an amine value of 5.0 to 25.0 mmol / g can be used. In the present invention, the polyethyleneimine-based compound refers to A. a polyethyleneimine compound, B. a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent, and C. a siloxane-modified polyethyleneimine compound. Note that when A to C are included, they are referred to as "polyethyleneimine-based compounds," and compounds included in "polyethyleneimine-based compounds" are referred to as "polyethyleneimine compounds," for example.
[0012] When laminating, the polyethyleneimine compound or siloxane-modified polyethyleneimine compound contained in the primer composition of the present invention preferably has a number average molecular weight of 1,000 to 200,000 from the viewpoint of strength. Of these, a number average molecular weight of 2,000 or more is preferred, and a number average molecular weight of 5,000 or more is more preferred. Furthermore, a number average molecular weight of 100,000 or less is preferred. The polyethyleneimine compound and siloxane-modified polyethyleneimine compound preferably have a mass average molecular weight of 4,000 to 800,000. Polyethyleneimine compounds having all of the amino groups in the molecule, from primary to tertiary amino groups, are preferred, and in particular, in terms of the content based on the number of each amino group, it is preferred that the secondary amino groups be more numerous than the primary and tertiary amino groups, and more preferably the content of secondary amino groups among all the primary to tertiary amino groups is 40% or more in terms of the number of groups. The more within these ranges, the easier the desorption can be achieved.
[0013] (A. Polyethyleneimine Compound and B. Polyethyleneimine Compound Common to Mixtures Containing a Polyethyleneimine Compound and a Glycidyl Group-Containing Silane Coupling Agent and / or an Isocyanate Group-Containing Silane Coupling Agent) The polyethyleneimine compound common to A and B preferably has an amine value of 10.0 mmol / g or more and 25.0 mmol / g or less. The polyethyleneimine compound common to A and B does not include C. siloxane-modified polyethyleneimine compound.
[0014] (B. Regarding the glycidyl group-containing silane coupling agent and / or isocyanate group-containing silane coupling agent in the mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent) In this case, one or more of the polyethyleneimine compounds mentioned above can be used as the polyethyleneimine compound. Examples of the silane coupling agent containing a glycidyl group include 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethoxydimethoxysilane, 3-glycidyloxypropylmethoxydiethoxysilane, 3-glycidyloxypropyltriethoxysilane, etc. Examples of the silane coupling agent containing an isocyanate group include 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 2-isocyanateethyltriethoxysilane, 2-isocyanateethyltrimethoxysilane, etc.
[0015] (C. Siloxane-modified polyethyleneimine compound) The siloxane-modified polyethyleneimine compound may be a compound containing polyethyleneimine and a compound of the formula: RZ-SiY3 and a silane coupling agent, which is at least one amine-reactive hydrolyzable organosilane represented by the formula: [wherein R represents an amine-reactive group selected from the group consisting of an isocyanate group, an oxiranyl group, a glycidoxy group, an acryloxy group, a carbethoxy group, a carbomethoxy group, a vinylsulfonyl group, and an acrylamide group; Z represents a divalent organic group containing a carbon atom; and each Y independently represents a hydrolyzable group]; and a silane coupling agent-modified polyethyleneimine compound, i.e., a siloxane-modified polyethyleneimine compound, which is obtained by reacting a component comprising: This siloxane-modified polyethyleneimine compound has a structure in which the group R of the silane coupling agent reacts with the amino group of the polyethyleneimine, and the silane coupling agent is bonded to the polyethyleneimine. The amine value of the siloxane-modified polyethyleneimine compound is preferably 5.0 mmol / g or more and 15.0 mmol / g or less. It should be noted that C. siloxane-modified polyethyleneimine compound is not included in the above A. polyethyleneimine compound and B. polyethyleneimine compound, and is a compound different from the polyethyleneimine compound.
[0016] (Polybutadiene compounds) In the present invention, the polybutadiene compound used in the detachment primer composition is preferably a hydroxyl group-containing polybutadiene compound and / or a carboxyl group-containing polybutadiene compound. Such polybutadiene compounds are preferably aqueous compositions. To make them aqueous and improve adhesion, hydroxyl- or carboxyl-containing polybutadiene compounds are preferred, in which hydroxyl or carboxyl groups are introduced into the polybutadiene compound. It is preferable that the polybutadiene compound is not crosslinked in order to exhibit releasability. Specific examples include EL-451 (Toyo-Morton Co., Ltd.) and T-180E (Nippon Soda Co., Ltd.). These compounds are sometimes used as anchor coating agents. When used as anchor coating agents, their sole purpose is to actively adhere or integrate a different composition with a substrate. However, the polybutadiene compound of the present invention does not simply function as an anchor coating agent, but rather possesses both releasability and adhesion as a primer composition, which are contradictory properties. In the present invention, by incorporating a polybutadiene compound, the retort resistance is slightly reduced, but the other effects of the present invention are excellent.
[0017] The coating amount of the polyethyleneimine compound and / or the polybutadiene compound on the resin substrate is 0.010 g / m 2 More than 0.015 g / m is preferable. 2 More preferably, 0.020 g / m or more 2 More preferably, the content is 0.400 g / m or more. 2 Preferably less than 0.300 g / m 2 Less than 0.200 g / m is more preferable. 2 More preferably, 0.100 g / m or less 2 The following are most preferred: The release primer composition may or may not contain polyolefin resin particles, inorganic metal salts, or organic metal salts.
[0018] <Method for producing a release primer composition> The release primer composition (1) can be obtained by adding a solvent to a polyethyleneimine compound and / or a polybutadiene compound and stirring them, or (2) can be obtained by adding a solvent to a polyethyleneimine compound and stirring them, and then adding a silane coupling agent containing a glycidyl group and / or a silane coupling agent containing an isocyanate group and stirring them. (3) can be obtained by adding a solvent to a siloxane-modified polyethyleneimine and / or a polybutadiene compound and stirring the mixture. The solvent can be a mixture of water and one or more alcohols such as methanol, ethanol, and isopropanol. When the detachment primer composition contains a polybutadiene compound, the detachment primer composition can be obtained by mixing the polybutadiene compound with the above-mentioned solvent by a known means.
[0019] [Resin substrate] The resin substrate in the present invention may be a substrate made of a known resin on whose surface printing can be performed. Examples of such a resin substrate include resin films of polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene (PE) and polypropylene (PP), polyamides such as nylon, the above-mentioned resin films having a metal layer such as aluminum, the above-mentioned resin films having a transparent vapor deposition layer, shrinkable polypropylene films (particularly shrinkable untreated polypropylene films), shrinkable polyvinyl chloride films, shrinkable polyethylene phthalate films, and other shrinkable plastic films. Furthermore, a laminate having a thermoplastic resin layer and an ethylene-based resin layer may or may not be used as the resin substrate. As such a resin substrate, there can be used resin films that serve as substrates for known lamination, resin films for surface printing or shrink printing, resin films laminated onto paper substrates, and the like, as described below. Furthermore, after forming a printing ink composition layer on a substrate via a detachable primer composition layer, the detachable primer composition of the present invention may be applied onto the printed layer, and a sealant layer may be formed by dry lamination or extrusion lamination.
[0020] [Print format] The detachment primer composition of the present invention is formed so as to be located between the surface of the resin substrate and the printing layer in a method of printing on a resin substrate. It is used in reverse printing, front printing, shrink printing, etc. Furthermore, in a printed matter in which the resin substrate, detachment primer layer, and printing layer are formed in this order, any known layer may be further formed between any of these layers or on the surface of the printed matter. When forming the resin substrate, detachment primer layer, adhesive layer, and paper substrate layer, any known layer may be further formed between any of these layers or on the surface of the resulting laminate. In addition, in a method in which an adhesive is applied to a base film and printing is performed on the paper base side of laminated paper to which the paper base is bonded, a removable primer layer is formed between the base film and the adhesive layer. Hereinafter, the printing formats in which the detachment primer composition of the present invention can be used will be described in the order of reverse printing, front printing, shrink printing, and printing on the paper substrate side of laminated paper in which an adhesive is applied to a substrate film and the paper substrate is bonded. However, the printing ink composition is not limited to the polyurethane resin described below, and may be any printing ink composition that forms a printing layer with excellent adhesion to a detachable primer layer or a paper substrate layer. Furthermore, ink compositions containing polyurethane resins, including those described below, acrylic resins, alkyd resins, modified alkyd resins, rosin-modified phenolic resins, and various binder resins, which are known to be used in ink compositions for gravure printing, flexographic printing, inkjet printing, and offset printing, can also be used. Furthermore, these ink compositions may be aqueous ink compositions, oil-based ink compositions, or ink compositions that cure with active energy rays such as ultraviolet rays or electron beams, and may also be aqueous or oil-based ink compositions that dry and solidify or heat-curable. Ink compositions that are retort-compatible when used in retort containers are more preferred. Furthermore, these ink compositions may be used for various purposes, such as front printing, back printing, and shrink printing. These ink compositions can be used for gravure printing, flexographic printing, inkjet printing, and offset printing.
[0021] (pigment) (Components that can be contained in reverse printing ink compositions, front printing ink compositions, and shrink printing ink compositions) In printing using the primer composition of the present invention, the pigment contained in the printing ink composition can be one or more of conventionally used inorganic and organic pigments. Examples of inorganic pigments include colored pigments such as titanium oxide, red iron oxide, antimony red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite, and examples of extender pigments include silica particles, calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. Of these, it is preferable to use titanium oxide as a white pigment. Examples of organic pigments include soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments. The content of these pigments in the printing ink composition is usually about 1 to 50% by mass. (A pigment used in ink compositions printed on the paper substrate side of laminated paper, which is made by applying an adhesive to a base film and bonding the paper substrate) As the pigment used in the ink composition to be printed on the paper substrate side, pigments that have been used conventionally in flexographic printing ink compositions can be used. Specific examples of inorganic pigments include colored pigments such as titanium oxide, red iron oxide, antimony red, cadmium yellow, cobalt blue, Prussian blue, ultramarine blue, carbon black, and graphite. Examples of organic pigments include soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments. These pigments can be used alone or in combination of two or more. The concentration of the pigment in the flexographic printing ink composition is 5 to 60% by mass, typically 6 to 35% by mass for organic pigments and 30 to 60% by mass for inorganic pigments.
[0022] [Print layer] <<Reverse printing>> The reverse printing ink composition for forming the printing layer of the present invention contains a binder resin and various additives in addition to the above-mentioned pigment. <Binder resin> The binder resin includes a polyurethane resin, preferably a polyurethane resin having an amine value from the viewpoints of the stability, adhesiveness and lamination suitability of the printing ink composition.
[0023] (Polyurethane resin) The polyurethane resin may contain a non-acid-modified polyurethane resin and / or an acid-modified polyurethane resin. A non-acid-modified polyurethane resin is a polyurethane resin that does not have acidic groups such as carboxylic acid groups, sulfonic acid groups, or phosphate groups at the molecular terminals and / or elsewhere in the molecule. An acid-modified polyurethane resin is a polyurethane resin that has acidic groups such as carboxylic acid groups, sulfonic acid groups, or phosphate groups at the molecular terminals and / or elsewhere in the molecule. The printed layer can be smoothly detached from the resin substrate whether the printed layer is formed from an ink composition using an acid-modified polyurethane resin as a vehicle or an ink composition using a resin that is inherently difficult to detach, such as a non-acid-modified polyurethane resin, as a vehicle.
[0024] As such a polyurethane resin, a polyurethane resin that is generally used in printing ink compositions can be used. Among these, polyurethane resins having amino groups (having an amine value) are preferred from the viewpoints of the stability over time, adhesion, and lamination suitability of the printing ink composition. Among polyurethane resins having amino groups, polyurethane resins having one or more types selected from primary amino groups, secondary amino groups, and tertiary amino groups at the molecular terminals, particularly one or more types selected from primary amino groups and secondary amino groups at the molecular terminals, are more preferred. More preferred is a polyurethane resin having a hydroxyl group and at least one type of amino group selected from a primary amino group, a secondary amino group and a tertiary amino group at the molecular terminal. The polyurethane resin has a specific functional group such as the amino group, and thus the reverse printing ink composition has excellent printability and adhesiveness. The amine value of the acid polyurethane resin is preferably 1.0 to 15.0 mgKOH / g, more preferably 2.0 to 8.0 mgKOH / g. If the amine value is less than 1.0 mgKOH / g, the adhesion of the printing ink composition for film of the present invention to the film may decrease, and further, the lamination suitability may decrease. If the amine value is more than 15.0 mgKOH / g, the blocking resistance may decrease. In the present invention, the amine value means the amine value per 1 g of solid content, and is determined by potentiometric titration (e.g., COMTITE (AUTO TITRA)) using a 0.1 N aqueous hydrochloric acid solution. This refers to the value measured using a TOR COM-900, BURET B-900, TITSTATION K-900, or Hiranuma Sangyo Co., Ltd., and then converted into the equivalent amount of potassium hydroxide. In addition, the polyurethane resin preferably has hydroxyl groups in the molecule and at the molecular terminals in terms of resolubility.
[0025] (non-acid-modified polyurethane resin) As the non-acid-modified polyurethane resin, a polyurethane polyurea resin and / or a polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound is preferred. The polyurethane polyurea resin is obtained by chain-extending and / or terminal-terminating a urethane prepolymer obtained from an organic diisocyanate component and a polymer diol component. The polyurethane polyurea resin obtained using the ketiminated compound is a polyurethane polyurea resin obtained by reacting a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound in an organic solvent with a urethane prepolymer as a chain extender and / or reaction terminator, or b. a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound in an organic solvent with a urethane prepolymer, stirring and mixing, adding water, and then carrying out chain extension and reaction termination to obtain a polyurethane polyurea resin. By using the above a and / or b, the amine odor of the resulting reverse printing ink composition is reduced and the stability over time is excellent. In consideration of the environment, the polyurethane polyurea resin may contain a biomass polyurethane polyurea resin.
[0026] (non-acid-modified polyurethane polyurea resin) The non-acid-modified polyurethane polyurea resin has at least one type of amino group selected from a primary amino group and a secondary amino group at the terminal of the molecule. More preferred is a non-acid-modified polyurethane polyurea resin having a hydroxyl group and at least one type selected from a primary amino group and a secondary amino group at the molecular terminal. As these polyurethane polyurea resins, polyurethane resins obtained by synthesizing a urethane prepolymer by reacting an organic diisocyanate compound with a polymeric diol compound and then reacting this with the chain extender and reaction terminator described below can be suitably used.
[0027] (Synthesis of urethane prepolymer) Each of the above urethane prepolymers is obtained by reacting the following organic diisocyanate compound with a polymeric diol compound.
[0028] (organic diisocyanate compounds) Examples of the organic diisocyanate compound include aromatic diisocyanate compounds such as tolylene diisocyanate, alicyclic diisocyanate compounds such as 1,4-cyclohexane diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4-diisocyanate (hydrogenated MDI), aliphatic diisocyanate compounds such as hexamethylene diisocyanate, and aralkyl diisocyanate compounds such as α,α,α',α'-tetramethylxylylene diisocyanate. These organic diisocyanate compounds can be used alone or in combination. Among these, alicyclic diisocyanate compounds, aliphatic diisocyanate compounds, and aralkyl diisocyanate compounds are more preferred.
[0029] Other organic diisocyanate compounds that can be used include aromatic diisocyanate compounds such as 1,3- and / or 1,4-phenylene diisocyanate, 4,4-diisocyanatobiphenyl, and 3,3-dimethyl-4,4-diisocyanatobiphenyl; alicyclic diisocyanate compounds such as cyclohexylene diisocyanate and methylcyclohexylene diisocyanate (hydrogenated TDI); aliphatic diisocyanate compounds such as ethylene diisocyanate, tetramethylene diisocyanate, dodecamethylene diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate; and aromatic aliphatic diisocyanate compounds such as m- and / or p-xylylene diisocyanate (XDI). When other organic diisocyanate compounds are used in combination, the number of isocyanate groups of the other organic diisocyanate compounds can be 50% or less, more preferably 30% or less, and even more preferably 10% or less, of the total number of isocyanate groups of all organic diisocyanate compounds. Alternatively, the amount of other organic diisocyanate compounds is 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of all organic diisocyanate compounds.
[0030] (polymeric diol compound) Examples of the polymer diol compound include polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polyether diol compounds such as alkylene oxide adducts of bisphenol A with ethylene oxide and propylene oxide, polyester diols obtained by condensation reaction of one or more dibasic acids such as adipic acid, sebacic acid, and phthalic anhydride with one or more glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, and 3-methyl-1,5-pentanediol, and polyester diol compounds such as polycaprolactone diols. These polymer diol compounds can be used alone or in combination. Furthermore, in addition to the above-mentioned high molecular weight diol compounds, alkanediols such as 1,4-pentanediol, 2,5-hexanediol, and 3-methyl-1,5-pentanediol, and low molecular weight diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, and 1,3-butanediol can be used alone or in combination by mixing two or more kinds.
[0031] The polymeric diol compound preferably has a number average molecular weight of 1,000 to 8,000, more preferably 1,000 to 5,500, and even more preferably 1,000 to 4,000. Furthermore, as the polymeric diol compound, one containing 3-methyl-1,5-pentylene adipate diol can be selected. In this case, the following polymeric diol compounds can be used in combination. Examples of polymeric diol compounds other than 3-methyl-1,5-pentylene adipate diol include polyester diols obtained by condensation reaction of one or more dibasic acids such as adipic acid, sebacic acid, and phthalic anhydride with one or more glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, and 3-methyl-1,5-pentanediol, polyester diol compounds such as polycaprolactone diols, and further polyalkylene glycols such as polyethylene glycol and polypropylene glycol, and polyether diol compounds such as alkylene oxide adducts of bisphenol A with ethylene oxide, propylene oxide, and the like. These polymeric diol compounds can be used alone or in combination of two or more.
[0032] Among the above, 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 1,000 to 8,000 obtained by a condensation reaction of adipic acid and 3-methyl-1,5-pentanediol is preferred, and 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 1,000 to 4,000 is more preferred. When other polymer diol compounds are used in combination, the number of hydroxyl groups of the other polymer diol compounds can be 70% or less, more preferably 55% or less, and even more preferably 40% or less, of the total number of hydroxyl groups of all polymer diol compounds. Alternatively, the amount of other polymer diol compounds is 50 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of all polymer diol compounds. When the organic solvent for the printing ink composition for reverse printing is a mixed solvent system of an ester-based solvent and an alcohol-based solvent (hereinafter sometimes referred to as a "mixed liquid") described below, using a polyether diol compound, preferably polypropylene glycol, as the polymer diol compound tends to increase the solubility of the resulting polyurethane resin and also tends to improve printing suitability such as gradation reproducibility and anti-fogging properties, making it possible to design a wide range of printing ink compositions to suit the required performance.
[0033] (non-acid-modified biomass polyurethane polyurea resin) The polyurethane resin may contain a biomass polyurethane polyurea resin that is not acid-modified, considering environmental considerations. The non-acid-modified biomass polyurethane polyurea resin will be described below. Note that, in the description of the non-acid-modified biomass polyurethane polyurea resin, descriptions common to the non-acid-modified polyurethane polyurea resin described above will be omitted as appropriate. Non-acid-modified biomass polyurethane polyurea resins are polyurethane resins containing biomass-derived (plant-derived) components. Non-acid-modified biomass polyurethane resins can contribute to preventing global warming and reducing environmental impact compared to resins made from other exhaustible resources. Non-acid-modified biomass polyurethane polyurea resins are preferably obtained by synthesizing a biomass urethane prepolymer by reacting a biopolyester polyol compound with an organic diisocyanate compound, and then reacting this with a chain extender and a reaction terminator as needed. It is more preferable that the isocyanate compound is a plant-derived bioisocyanate.
[0034] (Isocyanate compounds) In addition to the organic diisocyanates described above for the non-acid-modified polyurethane polyurea resin, vegetable oil-derived diisocyanates can also be used. Vegetable oil-derived organic diisocyanate compounds can be obtained by converting a plant-derived dicarboxylic acid into a terminal amino group through acid amidation and reduction, and then reacting it with phosgene to convert the amino group into an isocyanate group. Examples of plant-derived biopolyisocyanates include dimer acid diisocyanate (DDI), octamethylene diisocyanate, and decamethylene diisocyanate. Plant-derived isocyanate compounds can also be obtained by using plant-derived amino acids as raw materials and converting their amino groups into isocyanate groups. For example, lysine diisocyanate (LDI) can be obtained by methyl esterifying the carboxyl group of lysine and then converting the amino group into an isocyanate group. 1,5-pentamethylene diisocyanate can be obtained by decarboxylating the carboxyl group of lysine and then converting the amino group into an isocyanate group.
[0035] (biopolyester polyol compound) The biopolyester polyol compound (biomass polyester polyol) will be described below. In consideration of the environment, among the biopolyester polyol compounds, a biopolyester polyol compound obtained by synthesis from a material containing a plant-derived component may be used in combination as the other polymer diol compound. In addition, a non-acid-modified polyurethane polyurea resin obtained by reacting a polyester polyol compound including a biopolyester polyol compound with the above-mentioned specific isocyanate compound can also be mixed with the non-acid-modified polyurethane polyurea resin of the present invention and used. Therefore, the biopolyester polyol compound can be a biopolyester polyol obtained by reacting a short-chain diol compound having 2 to 4 carbon atoms with a carboxylic acid compound. It is more preferable that at least one of the short-chain diol compound and the carboxylic acid compound of the biopolyol component is plant-derived, and it is even more preferable that both are plant-derived. The plant-derived short-chain diol compound having 2 to 4 carbon atoms is not particularly limited. For example, the short-chain diol compound may be 1,3-propanediol, 1,4-butanediol, ethylene glycol, or the like, which are obtained from plant raw materials by the following method. These compounds may also be used in combination. 1,3-Propanediol can be produced from glycerol via 3-hydroxypropylaldehyde (HPA) by a fermentation method in which glucose is obtained by decomposing plant resources (e.g., corn). The 1,3-propanediol component produced by biomethods such as the fermentation method described above is safer than the 1,3-propanediol component produced by the EO production method, and useful by-products such as lactic acid are obtained. Furthermore, production costs can be kept low. 1,4-Butanediol can be produced by producing glycol from plant resources, fermenting it, and obtaining succinic acid, which is then hydrogenated. Furthermore, ethylene glycol can be produced via ethylene from bioethanol obtained by conventional methods.
[0036] The plant-derived carboxylic acid compound is not particularly limited. Examples of the carboxylic acid compound include sebacic acid, succinic acid, lactic acid, glutaric acid, and dimer acid. These may be used in combination. Among these, the carboxylic acid compound preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. Furthermore, 0.05 to 0.5 parts by mass of malic acid may be contained per 100 parts by mass of sebacic acid. Biopolyester polyol compounds are produced as 100% plant-derived biopolyester polyols by appropriately condensing a plant-derived short-chain diol compound with a plant-derived carboxylic acid. Specifically, polytrimethylene sebacate polyol is obtained by directly dehydrating and condensing plant-derived sebacic acid with plant-derived 1,3-propanediol. Furthermore, polybutylene succinate polyol is obtained by directly dehydrating and condensing plant-derived succinic acid with plant-derived 1,4-butanediol. One or more of these biopolyester polyol compounds may be used. The urethane prepolymer obtained using these plant-derived components may be contained in an amount of 10% by mass or more, or 40% by mass or more, calculated as solid content, of the total urethane prepolymer.
[0037] (Chain extenders and reaction terminators) Next, the chain extender and reaction terminator used in the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin will be described. The chain extender may be any known chain extender used in polyurethane polyurea resins as binders for printing ink compositions, and examples thereof include, among polyamine compounds, aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine; alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine; aromatic diamines such as toluylenediamine; aromatic aliphatic diamines such as xylenediamine; diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine (aminoethylethanolamine), N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine; and diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, diethylene glycol, and triethylene glycol. Furthermore, polyamine compounds such as diethylenetriamine and triethylenetetramine can be used in combination within a range that does not cause gelation of the polyurethane polyurea resin. Examples of reaction terminators that introduce primary and secondary amino groups into the terminals of polyurethane polyurea resins include polyamine compounds such as aliphatic diamines (e.g., ethylenediamine, propylenediamine, tetramethylenediamine, hexamethylenediamine), alicyclic diamines (e.g., isophoronediamine, 4,4'-dicyclohexylmethanediamine), polyamines (e.g., diethylenetriamine, triethylenetetratriamine), aromatic diamines (e.g., toluylenediamine), aromatic aliphatic diamines (e.g., xylenediamine), and diamines having hydroxyl groups (e.g., N-(2-hydroxyethyl)ethylenediamine (aminoethylethanolamine) and N-(2-hydroxyethyl)propylenediamine). Among these, polyamines having primary amino groups (e.g., diethylenetriamine, triethylenetetratriamine) are preferred. Examples of reaction terminators that introduce hydroxyl groups into polyurethane polyurea resins include alkanolamines such as monoethanolamine and diethanolamine, and diamines having hydroxyl groups such as N-(2-hydroxyethyl)ethylenediamine and N-(2-hydroxyethyl)propylenediamine. Also available are known reaction terminators, such as monoamine compounds and monoalcohol compounds. Specific examples include monoalkylamines such as n-propylamine and n-butylamine, dialkylamines such as di-n-butylamine, and monoalcohols such as ethanol.
[0038] The non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin can be produced by known polyurethane resin production methods using the above materials. Furthermore, since the hardness of the resulting polyurethane resin varies depending on the mass average molecular weight, chemical structure, and equivalent ratio of each component, it is possible to adjust the printability and lamination suitability by appropriately combining these components. The mass average molecular weight of the non-acid-modified polyurethane polyurea resin and non-acid-modified biomass polyurethane polyurea resin is preferably 10,000 to 70,000, and more preferably 20,000 to 60,000. Furthermore, in order to improve the flexibility and laminate strength, a polyurethane resin having no urea bond and a mass average molecular weight of 1,000 to 70,000 can be blended as the polyurethane resin.
[0039] (Reaction of organic diisocyanate compound with polymeric diol compound) Furthermore, when the organic diisocyanate compound and the polymeric diol compound are reacted, the respective use ratios, in terms of the equivalent ratio of isocyanate groups to hydroxyl groups (isocyanate index), are typically in the range of 1.2:1.0 to 3.0:1, and more preferably 1.3:1.0 to 2.0:1. If the isocyanate index is less than 1.2, the resulting resin will tend to be a flexible non-acid-modified polyurethane polyurea resin or a non-acid-modified biomass polyurethane polyurea resin, which may result in poor blocking resistance when the printing ink composition is printed, and in this case, it may be necessary to use the resin in combination with another hard resin.
[0040] A catalyst can be used during the reaction of an organic diisocyanate compound with a polymeric diol compound to obtain the non-acid-modified polyurethane polyurea resin or non-acid-modified biomass polyurethane polyurea resin used in the present invention. Among these, it is preferable to use an organometallic compound, and examples of such an organometallic compound include titanium compounds such as dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, and tributyltin. Examples of suitable compounds include tin compounds such as tin acetate, tributyltin chloride, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin trichloroacetate, and tin 2-ethylhexanoate, lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate, and further compounds such as iron 2-ethylhexanoate, iron acetylacetonate, cobalt benzoate, cobalt 2-ethylhexanoate, zinc naphthenate, zinc 2-ethylhexanoate, and zirconium naphthenate. Among these, titanium compounds such as tetrabutyl titanate are preferred. Tertiary amine compounds can also be used, such as triethylamine, triethylenediamine, 1,4-diazabicyclo(2,2,2)octane, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU).
[0041] (An acid-unmodified polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound, and an acid-unmodified biomass polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound) The non-acid-modified polyurethane polyurea resin obtained using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound, and the non-acid-modified biomass polyurethane polyurea resin obtained using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound can be produced by using a ketimine compound obtained by previously ketiminizing a polyamine compound with an excess amount of a ketone compound among the chain extenders and / or reaction terminators described above, c. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent and reacting it with a urethane prepolymer and / or a biomass urethane prepolymer, or d. employing a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent and adding it to the urethane prepolymer and / or a biomass urethane prepolymer and mixing with stirring, further adding water, and then carrying out chain extension and reaction termination. In particular, it is preferable to use one or more selected from the chain extenders and reaction terminators listed above: isophoronediamine, N-(2-hydroxyethyl)ethylenediamine, and ethylenediamine. The polyamine compound ketiminated with a ketone compound has a structure in which the oxygen atom of the ketone compound is substituted with the nitrogen atom of the amino group of the polyamine compound. The ketone compound to be used is preferably acetone, diethyl ketone, methyl ethyl ketone, diacetone alcohol, or methyl isobutyl ketone. In this ketiminization reaction, it is preferable not to use any solvent other than the ketone compound. However, as a solvent other than the ketone compound, an alcohol compound can be used, and among them, isopropanol can be used. The absence of any solvent other than the ketone compound is defined as "ketiminization under solvent-free conditions." Note that a polar organic solvent may be added instead of under solvent-free conditions, as long as it does not interfere with the subsequent chain extension reaction or the fact that the non-acid-modified polyurethane polyurea resin and the non-acid-modified biomass polyurethane polyurea resin do not have an odor. The present invention may also be a printing ink composition containing an unacid-modified polyurethane polyurea resin and / or an unacid-modified biomass polyurethane polyurea resin obtained by the chain extension or reaction termination process using a ketiminated chain extender and / or reaction terminator according to the method c or d above, wherein the printing ink composition and printed matter produced by the printing ink composition do not emit a ketimine odor. The printing ink composition also has the effect of increasing the peel strength when laminated to the printed surface by means of dry lamination, extrusion lamination, or the like. The ketiminated amine or the like may be used as a chain extender, a reaction terminator, or both a chain extender and a reaction terminator.
[0042] <Synthesis of an unacid-modified polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound, and an unacid-modified biomass polyurethane polyurea resin obtained by using a compound in which the amino group of a polyamine compound has been ketiminated with a ketone compound> A ketimine compound obtained by previously ketiminizing a polyamine compound with an excess amount of a ketone compound is used for a urethane prepolymer and / or biomass urethane prepolymer obtained by reacting an organic diisocyanate compound with a polymeric diol compound; e. A compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent is used and allowed to react with the urethane prepolymer and / or biomass urethane prepolymer; or f. A compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound in an organic solvent is used and added to the urethane prepolymer and / or biomass urethane prepolymer and mixed with stirring, and then water is added, followed by chain extension and reaction termination, thereby obtaining a non-acid-modified polyurethane polyurea resin and a non-acid-modified biomass polyurethane polyurea resin obtained using a compound in which the amino group of a polyamine compound has been ketiminized with a ketone compound. When a solvent is used in the reaction, an ester solvent and / or an alcohol solvent is preferred, a mixture of an ester solvent and an alcohol solvent is more preferred, propyl acetate and isopropanol are even more preferred, and a mass ratio of propyl acetate:isopropanol in the range of 1:1 to 5:1 is most preferred.
[0043] (Acid-modified polyurethane resin, acid-modified biomass polyurethane resin) The polyurethane resin in the present invention may be an acid-modified polyurethane resin and / or an acid-modified biomass polyurethane resin. These may be used together with the non-acid-modified polyurethane resin and / or non-acid-modified biomass polyurethane resin, or the acid-modified polyurethane resin and / or the acid-modified biomass polyurethane resin alone, or the non-acid-modified polyurethane resin and / or the non-acid-modified biomass polyurethane resin alone. The acid-modified polyurethane resin and the acid-modified biomass polyurethane resin can be obtained by a conventional method, such as by reacting the polymeric diol component with a tetrabasic acid anhydride such as pyromellitic anhydride, or by using a polymeric diol compound having a free carboxyl group obtained by ring-opening polymerization of lactones using an initiator such as dimethylolpropionic acid or dimethylolbutanoic acid, or by using a hydroxycarboxylic acid such as dimethylolpropionic acid or dimethylolbutanoic acid together with the polymeric diol compound that constitutes the polyurethane resin. The acid value of the acid-modified polyurethane resin and the acid-modified biomass polyurethane resin is preferably 70 mgKOH / g or less.
[0044] (Vinyl chloride-vinyl acetate copolymer) Vinyl chloride-vinyl acetate copolymers that may be incorporated into reverse printing ink compositions can be produced by known methods using the vinyl chloride monomer and vinyl acetate monomer that are conventionally used in gravure printing ink compositions as essential components, with optional copolymerization components such as vinyl propionate, vinyl monochloroacetate, vinyl versatate, vinyl laurate, vinyl stearate, and vinyl benzoate, and monomers having functional groups such as hydroxyl groups. Vinyl chloride-vinyl acetate copolymers with hydroxyl groups can be obtained by partially saponifying the acetate moieties and introducing (meth)acrylic monomers with hydroxyl groups. In the case of vinyl chloride-vinyl acetate copolymers with hydroxyl groups obtained by partial saponification of acetate ester moieties, the film properties and dissolution behavior of the resin are determined by the ratio of structural units based on the vinyl chloride reactive sites (Formula 1 below), structural units based on the vinyl acetate reactive sites (Formula 2 below), and structural units based on the saponification of the vinyl acetate reactive sites (Formula 3 below). Specifically, the structural units based on the vinyl chloride reactive sites impart toughness and hardness to the resin film, the structural units based on the vinyl acetate reactive sites impart adhesion and flexibility, and the structural units based on the saponification of the vinyl acetate reactive sites impart good solubility in the organic solvent systems of environmentally friendly printing ink compositions. Formula 1 -CH2-CHCl- Formula 2 -CH2-CH(OCOCH3)- Formula 3 -CH2-CH(OH)-
[0045] In addition, from the viewpoint of solubility in the organic solvents described below and printability used in the reverse printing ink composition, the vinyl chloride-vinyl acetate copolymer may have various functional groups in the molecule. When an environmentally friendly organic solvent is used, the vinyl chloride-vinyl acetate copolymer preferably has hydroxyl groups so that the hydroxyl value is 50 to 200 mgKOH / g. Commercially available vinyl chloride-vinyl acetate copolymers such as Solbin A, AL, TA5R, TA2, TA3, TAO, and TAOL are preferred.
[0046] (Vinyl chloride-acrylic copolymer) The vinyl chloride-acrylic copolymer that can be incorporated into the reverse printing ink composition is a copolymer of vinyl chloride and an acrylic monomer as the main component, and the form of the copolymer is not particularly limited. For example, the acrylic monomer may be incorporated in the main chain of polyvinyl chloride in a block or random manner, or may be graft copolymerized to the side chain of polyvinyl chloride.
[0047] The acrylic monomer may be a (meth)acrylic acid ester, an acrylic monomer having a hydroxyl group, etc. Examples of the (meth)acrylic acid ester include a (meth)acrylic acid alkyl ester, and the alkyl group may be linear, branched, or cyclic, but is preferably a linear alkyl group. For example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, and the like.
[0048] Examples of acrylic monomers having a hydroxyl group include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 1,4-cyclohexanedimethanol mono(meth)acrylate; caprolactone-modified (meth)acrylate; and hydroxyethyl acrylamide. The acrylic monomer may also have a functional group other than a hydroxyl group, such as a carboxyl group, an amide bond group, an amino group, or an alkylene oxide group. The vinyl chloride-acrylic copolymer preferably has a mass average molecular weight of 10,000 to 70,000. In addition, from the viewpoints of solubility in environmentally friendly organic solvents and adhesion to substrates, it is preferable that the vinyl chloride-acrylic copolymer has hydroxyl groups so that the hydroxyl value is 50 to 200 mgKOH / g.
[0049] The reverse printing ink composition may contain a polyurethane resin and (a vinyl chloride-vinyl acetate copolymer and / or a vinyl chloride-acrylic copolymer) in a mass ratio of polyurethane resin / (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) = 95 / 5 to 45 / 55, preferably 92 / 8 to 70 / 30. In addition, the ratio may be in the range of 90 / 10 to 75 / 25 for polyurethane resin / (vinyl chloride-vinyl acetate copolymer), and 95 / 5 to 85 / 15 for polyurethane resin / (vinyl chloride-acrylic copolymer). By containing a polyurethane resin and a vinyl chloride-vinyl acetate copolymer and / or a vinyl chloride-acrylic copolymer in a ratio of 95 / 5 to 45 / 55, the reverse printing ink composition has even better printability and adhesion to films, and also has better lamination suitability when lamination is performed. If the ratio of the polyurethane resin to the vinyl chloride-vinyl acetate copolymer and / or the vinyl chloride-acrylic copolymer exceeds 95 / 5, the proportion of the vinyl chloride-vinyl acetate copolymer and / or the vinyl chloride-acrylic copolymer may become small, and the adhesion to the film may become insufficient. On the other hand, if the polyurethane resin / (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) ratio is less than 45 / 55, the proportion of (vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer) will be high, and the printed matter formed using the printing ink composition will become hard, which may also result in insufficient adhesion to the film.
[0050] The combined content of the polyurethane resin and vinyl chloride-vinyl acetate copolymer and / or vinyl chloride-acrylic copolymer in the reverse printing ink composition is preferably 5 to 30% by mass. The reverse printing ink composition may also contain one or more agents selected from an adhesion improver and an anti-blocking agent, provided that the intended performance of the present invention is not impaired. Preferably, an adhesion improver and an anti-blocking agent are used in combination.
[0051] (adhesion improver) Examples of adhesion improvers that can be incorporated into the reverse printing ink composition include rosin and its derivatives, chlorinated polypropylene, and dammar resins. It is desirable to incorporate at least one, and more preferably two or more, selected from rosin and its derivatives.
[0052] (rosin and its derivatives) Examples of rosin include gum rosin, tall oil rosin, wood rosin, etc. Generally, rosin is an amber-colored, amorphous resin obtained from pine trees, and since it is obtained naturally, it is a mixture, but the constituent components, i.e., abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, sandaracopimaric acid, and dehydroabietic acid, may be isolated and used, and these are also defined as rosin in the present invention. The rosin derivatives are compounds obtained by modifying the above-mentioned rosin, and specific examples thereof are listed below. (1) Hydrogenated rosin: A rosin whose weather resistance has been improved by adding hydrogen to the conjugated double bonds (hydrogenation). (2) Disproportionated rosin: Disproportionation is a modification in which two molecules of rosin react with each other, resulting in two molecules of abietic acid with conjugated double bonds, one of which becomes aromatic and the other a molecule with a single double bond. Generally, disproportionated rosin is less weather-resistant than hydrogenated rosin, but its weather resistance is better than that of untreated rosin. (3) Rosin-modified phenolic resin: Rosin-modified phenolic resin is sometimes used as the main binder. Rosin-modified phenolic resin can be obtained by a known manufacturing method. (4) Rosin ester: An ester resin derived from rosin, which has long been used as a tackifier for adhesives and pressure sensitive adhesives. (5) Rosin-modified maleic acid resin: A resin obtained by adding maleic anhydride to rosin, and may also include a resin obtained by grafting a hydroxyl group-containing compound such as glycerin by esterification with the anhydride group, if necessary. (6) Polymerized rosin: A derivative containing dimerized resin acid derived from natural resin rosin. In addition, known rosins and rosin derivatives can also be used, and these can be used alone or in combination. Furthermore, the acid value of the rosin and its rosin derivatives is preferably 120 mgKOH / g or more. An acid value of 120 mgKOH / g or more improves laminate strength. An acid value of 160 mgKOH / g or more is even more preferable. Furthermore, the total amount of rosin and its derivatives used when blending is preferably 0.1 to 3.0 mass% in terms of solids mass% of the reverse printing ink composition.
[0053] (chlorinated polypropylene) Chlorinated polypropylenes having a chlorination degree of 20 to 50 can be used. Chlorinated polypropylenes with a chlorination degree of less than 20 tend to have reduced compatibility with organic solvents. On the other hand, chlorinated polypropylenes with a chlorination degree of more than 50 tend to have reduced adhesion to films. In the present invention, the chlorination degree is defined as the mass % of chlorine atoms in the chlorinated polypropylene resin. The chlorinated polypropylene is preferably a modified or unmodified chlorinated polypropylene having a mass average molecular weight of 5,000 to 200,000. If the mass average molecular weight is less than 5,000, the chlorinated polypropylene tends to have reduced adhesion. On the other hand, if the mass average molecular weight is more than 200,000, the chlorinated polypropylene tends to have reduced solubility in organic solvents. The amount of chlorinated polypropylene used when blended is preferably 0.1 to 3.0 mass % in terms of solid mass % of the reverse printing ink composition.
[0054] (Dammar resin) Dammar resin, also written as damar or dammar, is a type of natural resin derived from plants. Specifically, it is a type of natural resin obtained from Dipterocarpaceae or Burseraceae plants that grow in Southeast Asia, such as Malaysia and Indonesia. When used, it is dissolved in an appropriate organic solvent to form a varnish. Because dammar resin does not contain chlorine, it can eliminate or reduce chlorine compared to using chlorinated polypropylene in printing ink compositions. Furthermore, when incorporating dammar resin, the amount used is preferably 3.0 mass% or less, in terms of solids mass% of the reverse printing ink composition.
[0055] (Anti-blocking agent) Examples of anti-blocking agents include silica particles, polyethylene wax, fatty acid amides, cellulose acetate butyrate resins, cellulose acetate propionate resins, and soluble nitrocellulose. It is preferable to contain one or more, preferably two or more, of silica particles, polyethylene wax, and fatty acid amides, and depending on the type of pigment, it is preferable to further contain cellulose acetate butyrate resins, cellulose acetate propionate resins, and soluble nitrocellulose.
[0056] <Silica particles> Silica particles can be natural or synthetic, crystalline, amorphous, hydrophobic, or hydrophilic. The silica particles preferably have an average particle size of 1.0 to 5.0 μm (the average particle size of silica particles refers to the particle size at 50% cumulative value (D50) in the particle size distribution, and can be determined by the Coulter Counter method). The silica particles may be hydrophilic silica particles having hydrophilic functional groups on their surface, or hydrophobic silica particles in which the hydrophilic functional groups have been modified with alkylsilanes or the like to make them hydrophobic. However, hydrophilic particles are preferred. Printing ink compositions containing hydrophilic silica particles promote the wetting and spreading of the printing ink composition during overprinting, thereby improving the overprinting effect (hereinafter sometimes referred to as "trapping property"). The amount of silica particles used in the reverse printing ink composition is preferably 0.0 to 3.0% by mass, more preferably 0.1 to 1.0% by mass.
[0057] (polyethylene wax) It is preferable to use a polyethylene wax having an average particle size in the range of 1.0 to 3.0 μm (the average particle size refers to the particle size measured with a Honeywell Microtrac UPA). If the particle size of the polyethylene wax is smaller than 1.0 μm, the smoothness and anti-blocking properties may decrease, and if the particle size is larger than 3.0 μm, the trapping properties may decrease. The content of the polyethylene wax in the reverse printing ink composition is preferably in the range of 0.1 to 1.5% by mass. If the content is less than 0.1% by mass, the desired effect will not be achieved, and if the content is more than 1.5% by mass, the gloss may decrease.
[0058] (nitrocellulose) The soluble nitrocellulose can be one that has been used in gravure printing ink compositions. The soluble nitrocellulose is obtained by reacting natural cellulose with nitric acid to replace three hydroxyl groups in the six-membered ring of the anhydroglucopyranose group in the natural cellulose with nitric acid, resulting in a nitric acid ester. The soluble nitrocellulose used in the present invention preferably has a nitrogen content of 10 to 13% and an average degree of polymerization of 35 to 90. Specific examples include SS1 / 2, SS1 / 4, SS1 / 8, TR1 / 16, and NCRS-2 (Korea CNC Ltd.). The amount of soluble nitrocellulose used in the reverse printing ink composition is preferably in the range of 0.1 to 2.0% by mass, depending on the type of pigment.
[0059] (Cellulose acetate propionate resin) As the cellulose acetate propionate resin, resins that have been conventionally used in gravure printing ink compositions can be used. Cellulose acetate propionate resin is obtained by triesterifying cellulose with acetic acid and propionic acid, followed by hydrolysis. Resins with 0.6 to 2.5% by weight of acetylation, 42 to 46% by weight of propionylation, and 1.8 to 5% by weight of hydroxyl groups are generally commercially available. Cellulose acetate propionate resin is preferably used in the range of 0.1 to 3.0% by weight in the reverse printing ink composition, depending on the type of pigment.
[0060] (Cellulose acetate butyrate resin) As the cellulose acetate butyrate resin, resins that have been conventionally used in gravure printing ink compositions can be used. Cellulose acetate butyrate resins are obtained by triesterifying cellulose with acetic acid and butyric acid, followed by hydrolysis. Resins with 2 to 30% by mass of acetylation, 17 to 53% by mass of butyrylation, and 1 to 5% by mass of hydroxyl groups are generally commercially available. The amount of cellulose acetate butyrate resin used in the reverse printing ink composition is preferably in the range of 0.1 to 3.0% by mass, depending on the type of pigment.
[0061] (fatty acid amides) The fatty acid amide is not particularly limited as long as it has an amide group and a residue obtained by removing an acid group from a fatty acid. Examples of fatty acid amides include monoamides, substituted amides, bisamides, methylolamides, and esteramides. To improve blocking resistance, at least one selected from the group consisting of monoamides, substituted amides, and bisamides is preferred. The amount of fatty acid amide used in the reverse printing ink composition is preferably in the range of 0.01 to 1.0% by mass.
[0062] Monoamide: Monoamide is represented by the following general formula (1): General formula (1) R1-CONH2 (In the formula, R1 represents the residue obtained by removing COOH from a fatty acid.) Specific examples of monoamides include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, oleic acid amide, and erucic acid amide.
[0063] Substituted amide: The substituted amide is represented by the following general formula (2): General formula (2) R2-CONH-R3 (In the formula, R2 and R3 represent the residue obtained by removing COOH from a fatty acid, and may be the same or different.) Specific examples of the substituted amide include N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, and N-stearyl erucic acid amide.
[0064] Bisamide: Bisamide is represented by the following general formula (3) or (4). General formula (3) R4-CONH-R5-HNCO-R6 General formula (4) R7-NHCO-R8-CONH-R9 (In the formula, R4, R6, R7, and R9 represent residues obtained by removing COOH from fatty acids and may be the same or different, and R5 and R8 represent alkylene or arylene groups having 1 to 10 carbon atoms.) Specific examples of bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-distearyl adipamide, N,N'-distearyl sebacic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide.
[0065] Methylolamide: Methylolamide is represented by the following general formula (5): General formula (5) R 10 -CONHCH2OH (In the formula, R 10 represents the residue obtained by removing COOH from a fatty acid.) Specific examples of the methylol amide include methylol palmitic acid amide, methylol stearic acid amide, methylol behenic acid amide, methylol hydroxystearic acid amide, methylol oleic acid amide, and methylol erucic acid amide.
[0066] Ester amide: Ester amide is represented by the following general formula (6): General formula (6) R 11 -CONH-R 12 -OCO-R 13 (In the formula, R 11 and R 13 represents the residue obtained by removing COOH from a fatty acid, and may be the same or different, and R 12 represents an alkylene group or an arylene group having 1 to 10 carbon atoms. Specific examples of ester amides include stearylamide ethyl stearate and oleylamide ethyl stearate. The melting point of the fatty acid amide is preferably 50 to 150°C. Furthermore, the fatty acids constituting the fatty acid amide are preferably saturated fatty acids having 12 to 22 carbon atoms and / or unsaturated fatty acids having 16 to 25 carbon atoms, and more preferably saturated fatty acids having 16 to 18 carbon atoms and / or unsaturated fatty acids having 18 to 22 carbon atoms. Particularly preferred saturated fatty acids are lauric acid, palmitic acid, stearic acid, behenic acid, and hydroxystearic acid, and particularly preferred unsaturated fatty acids are oleic acid and erucic acid.
[0067] (organic solvent) The printing ink composition for reverse printing, which forms the printing layer, is oil-based. The organic solvents used are the same as those used in the ink compositions for front printing and shrink printing, and include, for example, alcohol-based solvents such as methanol, ethanol, isopropanol, normal propanol, butanol, isobutanol, and tert-butanol, aromatic hydrocarbon-based solvents such as toluene and xylene, aliphatic hydrocarbon-based solvents such as hexane, cyclohexane, methylcyclohexane, and ethylcyclohexane, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as ethyl acetate, n-propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, and tert-butyl acetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol dimethyl Examples of the esters include glycol solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether, and esters thereof, and as the esters, acetates are mainly selected, such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate. These can be used alone or in combination of two or more. From the viewpoint of environmental issues, it is preferable to use an ester-based organic solvent, a mixed solvent of an alcohol-based organic solvent and a ketone-based organic solvent, or a mixed solvent of an ester-based organic solvent and an alcohol-based organic solvent, which is more environmentally friendly. Furthermore, in order to improve wetting and spreading properties, the printing ink composition for reverse printing may contain 0.1 to 20 mass% of a glycol ether organic solvent relative to 100 mass% of the organic solvent. Specific examples of glycol ether organic solvents include ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, diethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol mono-n-propyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, and diethylene glycol diethyl ether. It is preferable that the reverse printing ink composition contains water to alleviate printing defects due to static electricity, prevent plate fogging, and improve cell reproducibility. The amount of water used in the reverse printing ink composition is preferably 10% by mass or less, and more preferably in the range of 0.1 to 5.0% by mass.
[0068] (Other ingredients) The reverse printing ink composition may further contain various additives such as a pigment dispersant, an antistatic agent, and a plasticizer. A printing ink composition can be produced using the above-mentioned constituent materials by any known method, for example, by grinding a mixture of a binder resin, an organic solvent, and, if necessary, a pigment dispersant, etc., using a high-speed mixer, a ball mill, a sand mill, an attritor, etc., and then adding and mixing the remaining materials, such as a thiocyanate and predetermined additives. Furthermore, a metal tetraalkoxide and / or a hydroxy acid may or may not be contained.
[0069] (Method for producing reverse printing ink composition) A method for producing a printing ink composition for reverse printing using these materials involves first stirring and mixing the pigment, binder resin, organic solvent, and, if necessary, pigment dispersant, surfactant, etc., and then milling the mixture using a mill such as a bead mill, ball mill, sand mill, attritor, roll mill, or pearl mill, and then adding and mixing the fatty acid amide, chelating crosslinker, and remaining materials.
[0070] (Printing method using reverse printing ink composition and laminate obtained thereby) Next, a method for obtaining a laminate print using the reverse printing ink composition will be described. The reverse printing ink composition can also be used for purposes other than lamination. Methods for obtaining laminated prints include at least the following printing methods. For example, the release primer composition of the present invention is applied to a resin substrate, such as a resin film that serves as a known substrate for lamination. Thereafter, a gravure printing ink composition for lamination is printed one or more times by gravure printing, either inline or offline. Next, another gravure lamination printing ink composition is printed by gravure printing at any location on the surface side of the gravure lamination printing ink layer formed by these printings (the lower layer side from the surface layer after final lamination), and the resulting printed layer is dried with a dryer. A resin film or the like can be laminated by various methods on the layer of the gravure laminate printing ink composition of the printed matter obtained by the above method to form a sealant layer, thereby obtaining a laminated printed matter for packaging bags, etc. Examples of lamination methods that can be used include extrusion lamination, in which a molten polymer is laminated on the surface of the printed matter, with or without coating an anchor coating agent, and dry lamination, in which an adhesive is applied to the surface of the printed matter, and then a film-like polymer is attached. The extrusion-laminated resin layer or film-like polymer can be made of resin such as unstretched polypropylene or VMCPP (aluminum-deposited unstretched polypropylene). In particular, in the latter case, the sealant layer, VMCPP itself, can be removed in the removal step using the remover solution described below.
[0071] The extrusion lamination method involves laminating a molten polymer using a known extrusion laminator on the surface of a printed material containing a layer of a printing ink composition, after or without coating an anchor coating agent such as a titanium-based, urethane-based, imine-based, or polybutadiene-based agent as needed, and the molten resin can also be sandwiched and laminated with other materials as an intermediate layer. In this case, it is not necessary to use a polyethyleneimine-based anchor coating agent. The molten polymer used in the extrusion lamination method may be a conventionally used resin such as low-density polyethylene, ethylene-vinyl acetate copolymer, polypropylene, etc. Among these, the effect of the present invention is enhanced when low-density polyethylene is used, which is prone to generate carbonyl groups due to oxidation during melting.
[0072] The dry lamination method involves applying a urethane-based, isocyanate-based, or other adhesive to the surface of a layer made from a gravure laminate printing ink composition, followed by laminating a resin film using a known dry laminating machine. To obtain packaging materials for retort pouches, aluminum foil can be sandwiched between the substrate and the resin film. Such laminated products can also be used for boiling and retort pouches after being filled with the contents. Examples of the resin film used in this case include oriented and unoriented polyolefins such as polyethylene and polypropylene, polyester, nylon, cellophane, vinylon, etc. Furthermore, with regard to these resin films, films obtained by processing in advance such as coating or kneading in an anti-fogging agent, or surface coating or kneading in a matting agent can also be used. Furthermore, as the resin film, films in which a barrier layer formed by metal deposition or coating a barrier resin on various printing plastic films can be used.
[0073] <<Surface printing>> The surface printing ink composition contains the above pigment, a binder resin and various additives. <Binder resin> The binder resin contained in the surface printing ink composition can be selected from the following resins, for example, a combination of cellulose resin and polyamide resin, a combination of cellulose resin and polyurethane resin, a combination of polyurethane resin and the above-mentioned vinyl chloride-vinyl acetate copolymer, a combination of acrylic resin and polyurethane resin, a combination of cellulose resin and acrylic resin, cellulose resin alone, or the above-mentioned vinyl chloride-vinyl acetate copolymer alone.
[0074] (cellulose-based resin) The cellulose-based resin can be any cellulose-based resin that has been conventionally used in gravure printing ink compositions. Examples of such cellulose-based resins include lower acyl-substituted cellulose resins such as nitrocellulose (nitro group-substituted), cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate (CAB), and lower alkyl-substituted cellulose resins such as methyl cellulose and ethyl cellulose. These cellulose-based resins, such as those with a mass-average molecular weight and a degree of hydroxyl group substitution that fall within the ranges used in ordinary printing ink compositions and paints, can be used in the present invention without any problems.
[0075] The degree of substitution of hydroxyl groups is preferably about 1.3 to 2.7. In addition, from the viewpoint of heat resistance, the use of nitro group-substituted compounds is advantageous, and from the viewpoint of adhesiveness, lower acyl group-substituted compounds and lower alkyl group-substituted compounds are advantageous, so it is preferable to select and use an appropriate compound depending on the purpose. When a cellulose-based resin is contained, the content ratio of the polyurethane resin to the cellulose-based resin is preferably polyurethane resin:cellulose-based resin = 5:95 to 95:5 by mass. The content ratio of the polyamide resin to the cellulose-based resin is preferably polyamide resin:cellulose-based resin = 95:5 to 70:30. The content ratio of the acrylic resin to the cellulose-based resin is preferably acrylic resin:cellulose-based resin = 95:5 to 30:70.
[0076] (Polyurethane resin) As the polyurethane resin, a polyurethane resin obtained by reacting a polyisocyanate compound, a diol compound, and, if necessary, a chain extender, a reaction terminator, etc. can be used. Examples of the polyisocyanate compound that can be used include aliphatic diisocyanate compounds such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as isophorone diisocyanate, hydrogenated xylylene diisocyanate and 4,4-cyclohexylmethane diisocyanate; aromatic aliphatic diisocyanate compounds such as xylylene diisocyanate and α,α,α',α'-tetramethylxylylene diisocyanate; and aromatic diisocyanate compounds such as toluylene diisocyanate and diphenylmethane diisocyanate. Furthermore, known binder resins for gravure printing can be used in combination with such polyurethane resins.
[0077] Next, suitable diol compounds are polymeric diol compounds, preferably having a number-average molecular weight of more than 500 and not more than 3,000, more preferably 500 to 2,000, and may consist of one type of diol compound or may contain a combination of multiple diol compounds. If the number-average molecular weight of the diol compound is 500 or less, adhesiveness tends to decrease, while if the number-average molecular weight exceeds 3,000, oil resistance tends to decrease. Specific examples of the diol compound include alkylene glycol compounds having a number average molecular weight of 100 or more, polyalkylene glycol compounds such as polyethylene glycol and polypropylene glycol, and polyether diol compounds obtained by polyaddition of a diol compound such as a low-molecular-weight alkylene glycol or bisphenol with an oxyalkylene such as ethylene oxide or propylene oxide, or tetrahydrofuran. Other examples include polyester diol compounds obtained by polycondensation of low-molecular-weight diol compounds such as linear glycols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol; branched glycols such as 1,2-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and ethylbutylpropanediol; and ether-based diols such as diethylene glycol and triethylene glycol, with dicarboxylic acid compounds such as saturated and unsaturated aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and maleic acid, and aromatic dicarboxylic acids such as phthalic acid; and polyester diol compounds obtained by ring-opening reaction of cyclic ester compounds such as lactones.
[0078] Furthermore, linear or side chain polycarbonate compounds, polybutadiene glycol compounds, etc. can also be used in combination. In addition, in consideration of the environment, it is preferable to use a polyether diol compound as the polyol compound in order to obtain good printability in a system that does not contain aromatic hydrocarbon organic solvents (toluene, etc.) and that contains a high proportion of highly polar organic solvents such as alcohols and esters. When other solvents are used, it may be preferable to use a polyester diol compound.
[0079] Furthermore, it is also possible to use a polyurethane resin obtained using a chain extender or a reaction terminator. Examples of chain extenders include aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine; alicyclic diamines such as isophoronediamine and 4,4'-dicyclohexylmethanediamine; polyamines such as diethylenetriamine and triethylenetetratriamine; aromatic diamines such as toluylenediamine; aromatic aliphatic diamines such as xylenediamine; diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine, N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine; and diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, diethylene glycol, and triethylene glycol.
[0080] Examples of the reaction terminator include monoalcohols such as methanol and ethanol, alkylamines such as n-propylamine, n-butylamine, and di-n-butylamine, alkanolamines such as monoethanolamine and diethanolamine, aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, and hexamethylenediamine, alicyclic diamines such as isophoronediamine, 1,4-butanediamine, and 4,4'-dicyclohexylmethanediamine, polyamines such as diethylenetriamine and triethylenetetratriamine, aromatic diamines such as toluylenediamine, aromatic aliphatic diamines such as xylenediamine, diamines having a hydroxyl group such as N-(2-hydroxyethyl)ethylenediamine, N-(2-hydroxyethyl)propylenediamine, and N,N'-di(2-hydroxyethyl)ethylenediamine, and aminoethylethanolamine.
[0081] To obtain the polyurethane resin used in the present invention using the above synthesis components, first, the polyisocyanate compound NCO and the diol compound OH are reacted so that the molar equivalent ratio (equivalent of NCO of polyisocyanate compound / equivalent of OH of diol compound) is 0.5 or more and 3.0 or less, preferably 1.2 or more and 1.5 or less, and then, if necessary, a chain extender and a reaction terminator are reacted. If the NCO equivalent of the polyisocyanate compound / the OH equivalent of the diol compound is less than 0.5, the heat resistance and oil resistance tend to decrease, whereas if the NCO equivalent of the polyisocyanate compound / the OH equivalent of the diol compound is more than 3, the stretchability tends to decrease.
[0082] (Biomass polyurethane) In consideration of environmental aspects, a part or all of the diol compounds constituting the polyurethane may be diol compounds obtained using biomass components derived from plant components. As such a diol compound, a polyester polyol compound is preferred, and as this polyester polyol compound, a biopolyester polyol obtained by reacting a short-chain diol compound having 2 to 4 carbon atoms with a carboxylic acid compound can be used. It is more preferred that at least one of the short-chain diol compound and the carboxylic acid compound of the biopolyol component is plant-derived, and it is even more preferred that both are plant-derived. The plant-derived short-chain diol compound having 2 to 4 carbon atoms is not particularly limited. For example, the short-chain diol compound may be 1,3-propanediol, 1,4-butanediol, ethylene glycol, or the like, which are obtained from plant raw materials by the following method. These compounds may also be used in combination. 1,3-Propanediol can be produced from glycerol via 3-hydroxypropylaldehyde (HPA) by a fermentation method in which glucose is obtained by decomposing plant resources (e.g., corn). The 1,3-propanediol component produced by biomethods such as the fermentation method described above is safer than the 1,3-propanediol component produced by the EO production method, and useful by-products such as lactic acid are obtained. Furthermore, production costs can be kept low. 1,4-Butanediol can be produced by producing glycol from plant resources, fermenting it, and obtaining succinic acid, which is then hydrogenated. Furthermore, ethylene glycol can be produced via ethylene from bioethanol obtained by conventional methods.
[0083] The plant-derived carboxylic acid compound is not particularly limited. Examples of the carboxylic acid compound include sebacic acid, succinic acid, lactic acid, glutaric acid, and dimer acid. These may be used in combination. Among these, the carboxylic acid compound preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. Furthermore, 0.05 to 0.5 parts by mass of malic acid may be contained per 100 parts by mass of sebacic acid. Biopolyester polyol compounds are produced as 100% plant-derived biopolyester polyols by appropriately condensing a plant-derived short-chain diol compound with a plant-derived carboxylic acid. Specifically, polytrimethylene sebacate polyol is obtained by directly dehydrating and condensing plant-derived sebacic acid with plant-derived 1,3-propanediol. Furthermore, polybutylene succinate polyol is obtained by directly dehydrating and condensing plant-derived succinic acid with plant-derived 1,4-butanediol. One or more of these biopolyester polyol compounds may be used. The urethane prepolymer obtained from these plant-derived components may be contained in an amount of 10% by mass or more, or 40% by mass or more, calculated as solid content, of the total urethane prepolymer. Even when plant-derived components are used in this way, the same chain extenders and reaction terminators as those described above can be used.
[0084] (Polyamide resin) The polyamide resin is obtained by reacting an acid component, which may mainly contain polymerized fatty acids and may further contain aliphatic, alicyclic, and aromatic dicarboxylic acids and aliphatic monocarboxylic acids, with an amine component, which may mainly contain aliphatic, alicyclic, araliphatic, and aromatic polyamines alone or in mixtures, and may further contain primary and secondary monoamines. Here, polymerized fatty acids are generally obtained by polymerizing unsaturated fatty acids or their esters having 16 to 22 carbon atoms, and include monobasic fatty acids, dimerized polymerized fatty acids, trimerized polymerized fatty acids, etc. Examples of aliphatic dicarboxylic acids include succinic acid, adipic acid, azelaic acid, maleic acid, etc. Examples of alicyclic dicarboxylic acids include cyclohexanedicarboxylic acid, etc. Examples of aromatic dicarboxylic acids include isophthalic acid, terephthalic acid, etc. Examples of aliphatic monocarboxylic acids include acetic acid, stearic acid, oleic acid, linoleic acid, etc.
[0085] On the other hand, among the amine components, examples of aliphatic polyamines include aliphatic diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, and methylaminopropylamine, and aliphatic polyamines such as diethylenetriamine and triethylenetetramine. Examples of alicyclic polyamines include cyclohexylenediamine and isophoronediamine. Examples of aromatic aliphatic polyamines include xylylenediamine, and examples of aromatic polyamines include phenylenediamine and diaminodiphenylmethane. Examples of primary and secondary monoamines include butylamine, octylamine, diethylamine, monoethanolamine, monopropanolamine, diethanolamine, and dipropanolamine. From the viewpoint of oil resistance, heat resistance, and PVC blocking resistance of the printing ink composition, it is preferable to use a polyamide resin that uses an alkanolamine as the primary or secondary monoamine component and has a hydroxyl group in the molecule. In the method for synthesizing a polyamide resin from the above-mentioned acid component and amine component, the ratio of carboxyl groups to amino groups in the reaction components is preferably 0.9 / 1.0 to 1.0 / 0.9, more preferably 1.0 / 1.0, the reaction temperature is preferably 160 to 280°C, even more preferably 180 to 230°C, and the reaction is desirably carried out under reduced pressure of about 100 torr in the final stage.
[0086] (Thermoplastic polyamide resin made from vegetable oil fatty acids as a reaction raw material) Among the above polyamide resins, thermoplastic polyamide resins using vegetable oil fatty acids as reaction raw materials are not particularly limited. For example, thermoplastic polyamide resins using vegetable oil fatty acids as reaction raw materials include polyamide resins using vegetable oil fatty acids such as tall oil, rice bran oil, palm oil, coconut oil, and soybean oil as reaction raw materials. By using vegetable oil fatty acids as reaction raw materials, the environmental impact of using such thermoplastic polyamide resins can be reduced. The thermoplastic polyamide resin using vegetable oil fatty acids as a reaction raw material is a polycondensation product of a polycarboxylic acid containing vegetable oil fatty acids and a polyamine. The polyamine is not particularly limited. Examples of the polyamine include aliphatic polyamines, alicyclic polyamines, and aromatic polyamines. Examples of the aliphatic polyamines include ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexane, piperazine, and N-aminoethylpiperazine. Examples of the alicyclic polyamines include isophoronediamine and bisaminomethylcyclohexane. Examples of the aromatic polyamines include metaxylenediamine. The thermoplastic polyamide resins may be used in combination. The number average molecular weight (Mn) of the thermoplastic polyamide resin is not particularly limited. For example, the Mn of the thermoplastic polyamide resin is preferably 1,000 or more. Also, the Mn is preferably 30,000 or less. If the Mn of the thermoplastic polyamide resin is less than 1,000, the printing ink composition tends to have reduced blocking resistance and heat resistance. On the other hand, if the Mn is more than 30,000, the printing ink composition tends to have reduced crump resistance. The acid value and amine value of the thermoplastic polyamide resin are not particularly limited. For example, the acid value of the thermoplastic polyamide resin is preferably 10.0 mg KOH / g or less, and the amine value is preferably 5.0 mg KOH / g or less. The softening point of the thermoplastic polyamide resin is more preferably 90 to 150°C. The content of the thermoplastic polyamide resin is not particularly limited. For example, the content of the thermoplastic polyamide resin is preferably 20.0 mass % or more and 70.0 mass % or less based on the total solid content in the printing ink composition.
[0087] (acrylic resin) The acrylic resin can be produced by a conventionally known method, and the production method is not particularly limited. The acrylic resin is obtained by polymerizing a monomer having a carbon-carbon unsaturated double bond in one molecule in a solvent in the presence of a polymerization initiator. Examples of the monomer having a carbon-carbon unsaturated double bond in one molecule include (i) (meth)acrylic acid derivatives, (ii) aromatic vinyls, (iii) olefinic hydrocarbons, (iv) vinyl esters, (v) vinyl halides, and (vi) vinyl ethers.
[0088] (i) Examples of (meth)acrylic acid derivatives include (meth)acrylonitrile, (meth)acrylate salts, alkyl (meth)acrylates such as methyl (meth)acrylate, butyl (meth)acrylate, ethylhexyl (meth)acrylate, and stearyl (meth)acrylate, and benzyl (meth)acrylate. (ii) Examples of aromatic vinyls include styrenes in which some hydrogen atoms have been substituted with fluorine, such as styrene, methylstyrene, ethylstyrene, chlorostyrene, monofluoromethylstyrene, difluoromethylstyrene, and trifluoromethylstyrene. (iii) Examples of olefinic hydrocarbons include ethylene, propylene, butadiene, isobutylene, isoprene, and 1,4-pentadiene. (iv) Examples of vinyl esters include vinyl acetate. (v) Examples of vinyl halides include vinyl chloride and vinylidene chloride. (vi) Examples of vinyl ethers include vinyl methyl ether. Furthermore, a monomer having a crosslinkable functional group can be used as the monomer having a carbon-carbon unsaturated double bond in one molecule. Examples of the monomer having a functional group include (vii) a monomer having a hydroxyl group, (viii) a monomer having an isocyano group, and (ix) a monomer having an epoxy group.
[0089] (vii) Examples of monomers having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and polytetramethylene glycol mono(meth)acrylate; and hydroxystyrene. (viii) Examples of monomers having an isocyano group include (meth)acryloyloxyethyl isocyanate, (meth)acryloyloxypropyl isocyanate, and the like, as well as those obtained by reacting a hydroxyalkyl (meth)acrylate, such as 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate, with a polyisocyanate, such as toluene diisocyanate or isophorone diisocyanate. (ix) Examples of monomers having an epoxy group include glycidyl methacrylate, glycidyl cinnamate, glycidyl allyl ether, glycidyl vinyl ether, vinylcyclohexane monoepoxide, and 1,3-butadiene monoepoxide. If necessary, one or more of these monomers having a carbon-carbon unsaturated double bond in one molecule can be used, and the acid value is preferably 100 to 200 mgKOH / g. If the acid value is outside this range, the printing ink may undergo phase separation, an increase in viscosity, or gelation, resulting in problems with storage stability. The hydroxyl value is preferably 20 to 110 mgKOH / g. As the polymerization initiator used in synthesizing the acrylic resin, a typical peroxide or azo compound, such as benzoyl peroxide, azoisobutylvalenonitrile, azobisisobutyronitrile, di-t-butyl peroxide, t-butyl perbenzoate, t-butyl peroctoate, or cumene hydroxyperoxide, is used, and the polymerization temperature is 50 to 140°C, preferably 70 to 140°C. The mass average molecular weight of the resulting polymer is preferably 5,000 to 100,000. The non-aromatic solvent used in the above production method may be a ketone such as acetone, methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone, an ether such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, or diethylene glycol dimethyl ether, or an ester such as ethyl acetate or butyl acetate, etc. The solvent may be a mixture of two or more kinds.
[0090] (rosin resin and its derivatives) The rosin-based resin can be arbitrarily selected from rosins and their derivatives that can be used in the reverse printing described above. Among these, the rosin resin preferably has an acid value of 10 to 350 mgKOH / g, more preferably 200 to 350 mgKOH / g, and even more preferably 250 to 350 mgKOH / g. Among the rosin resins, rosin maleic acid resin and / or polymerized rosin are preferred. The content of the rosin resin in the printing ink composition is preferably 0.1 to 5.0% by mass.
[0091] (other resins) Other resins that may be used as needed in surface printing ink compositions include vinyl chloride / vinyl acetate resins, dimer acid resins, rosin resins, maleic acid resins, petroleum resins, terpene resins, ketone resins, dammar resins, copal resins, chlorinated polypropylene, and polypropylene oxide. The use of these hard resins is expected to improve adhesion, especially to resin films that have not been surface-treated. The appropriate amount of hard resin to be included in a gravure printing ink composition is less than 5.0% by mass. However, when using vinyl chloride-vinyl acetate resin, the solid content ratio of polyurethane resin to vinyl chloride-vinyl acetate resin is preferably polyurethane resin / vinyl chloride-vinyl acetate resin = 100 / 0 to 70 / 30, and more preferably 100 / 0 to 10.
[0092] (chelating crosslinker) As the chelate crosslinking agent, a metal chelate crosslinking agent such as titanium chelate or zirconium chelate can be used. Examples of titanium chelates include titanium alkoxides such as tetraisopropyl titanate, tetra-normal-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, a reaction product of tetraisopropoxytitanium with 2-ethylhexanoic acid, tetramethyl titanate, and tetrastearyl titanate, as well as titanium chelates such as triethanolamine titanate, titanium acetylacetate, titanium ethylacetoacetate, titanium lactate, octylene glycol titanate, titanium tetraacetylacetonate, n-butyl phosphate ester titanium, and propanedioxytitanium bis(ethyl acetylacetate). Examples of zirconium chelates include zirconium propionate and zirconium acetylacetate. From an environmental viewpoint, among chelating crosslinking agents, a chelating crosslinking agent that does not have acetylacetonate as a ligand is preferred so as not to generate acetylacetone after the crosslinking reaction.
[0093] (fatty acid amides) Fatty acid amides are used from the viewpoint of blocking resistance. Examples of fatty acid amides include saturated fatty acid amides, unsaturated fatty acid amides, and modified fatty acid amides. To improve blocking resistance to soft polyvinyl chloride sheets used in tablecloths, it is particularly preferable to use modified fatty acid amides. When fatty acid amides are included, their content in the printing ink composition is preferably 0.1 to 3.0 mass %, more preferably 0.5 to 2.0 mass %. If the content is less than 0.1% by mass, blocking resistance may decrease, and if it exceeds 3.0% by mass, oil resistance may decrease.
[0094] (organic solvent) The solvent component used in the front-side printing ink composition for forming the front-side printing layer can be any of the solvents that can be used in the reverse-side printing ink composition. Furthermore, for environmental reasons, it is preferable to use an organic solvent that does not contain an aromatic hydrocarbon organic solvent. Examples of organic solvents that do not contain an aromatic hydrocarbon organic solvent include alcohol organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol; ketone organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; aliphatic hydrocarbon organic solvents such as n-hexane, n-heptane, and n-octane; and alicyclic hydrocarbon organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane. Mixtures of these organic solvents can also be used, taking into account the solubility and drying properties of the binder resin. However, from an environmental perspective, it is preferable to avoid ketone organic solvents as much as possible among the above organic solvents. In consideration of printability, the amount of these organic solvents used in the printing ink composition of the present invention is preferably 15.0% by mass or more. Furthermore, from the viewpoint of printability, it is preferable that propyl acetate is contained in the printing ink composition in an amount of more preferably 5.0% by mass or more, and even more preferably 10.0% by mass or more. Furthermore, in order to improve printability, it is preferable that 0.1 to 10% by mass of water is contained in the organic solvent.
[0095] <Pigments> The above-mentioned pigments can be contained in the surface printing ink composition.
[0096] (Other ingredients) Wax may be added to the surface printing ink composition to improve rub resistance, provided that the performance is not impaired. As the wax, various known waxes such as polyolefin wax and paraffin wax can be used. Furthermore, various printing ink additives such as pigment dispersants, leveling agents, surfactants, plasticizers, etc. may be added as desired.
[0097] (Method for producing surface printing ink composition) As a method for producing a printing ink composition for front printing using these materials, the same method as the method for producing a printing ink composition for reverse printing described above can be adopted.
[0098] (Printing method using surface printing ink composition and laminate obtained thereby) Next, a method for obtaining a surface-printed matter using the surface-printing ink composition will be described. A release primer layer is formed on a resin substrate for surface printing using the release primer composition of the present invention. Then, the surface printing ink composition is printed inline or offline using a conventional surface printing method. The printing speed and drying temperature can be appropriately selected from known speeds and temperatures. The resin substrate may be the same as that used for reverse printing.
[0099] <<Printing for shrink packaging>> The ink composition for shrink packaging contains the above pigment, a binder resin and various additives.
[0100] <Binder resin> Usable binder resins include, for example, carboxyl group-containing acrylic resins, cellulose resins, rosin resins and their derivatives, and printing ink compositions for shrink packaging containing urethane resins, which satisfy the following conditions 1 and 2. Condition 1: The ratio of the solid content mass of the carboxyl group-containing acrylic resin to the solid content mass of the cellulose resin is 80 / 20 to 60 / 40. Condition 2: The rosin resin and its derivatives have an acid value of 150 mgKOH / g or less, and are contained in the range of 1 to 6 mass % in the resin solid content. The printing ink composition for shrink packaging of the present invention will be specifically described below. The biomass degree of the printing ink composition for shrink packaging of the present invention is preferably 10 or more. The biomass ratio is calculated using the following formula: Biomass content = biomass component amount / total solids including pigment in shrink packaging printing ink composition × 100 Biomass components: Total weight of biomass-derived components in resin solids and additive solids (resin weight x biomass weight ratio + additive weight x biomass weight ratio)
[0101] (acid number) The acid value in the present invention is determined by calculating the theoretical amount of potassium hydroxide (KOH) to neutralize the amount of each monomer theoretically required to obtain 1 g of a carboxyl group-containing acrylic resin, rosin resin, etc., and the total number of mg of the neutralized amounts is taken as the acid value of the polymer.
[0102] <Mass average molecular weight> The mass average molecular weight of the resin in the present invention can be measured by gel permeation chromatography (GPC). For example, chromatography is performed using a Water 2690 (Waters) GPC apparatus, a PLgel 5μ MIXED-D (Polymer Laboratories) column, tetrahydrofuran as the developing solvent, a column temperature of 25°C, a flow rate of 1 ml / min, an RI detector, a sample injection concentration of 10 mg / ml, and an injection volume of 100 μl, and the mass average molecular weight is determined as polystyrene equivalent.
[0103] (carboxyl group-containing acrylic resin) Examples of the carboxyl group-containing acrylic resin include a copolymer of a radically polymerizable carboxylic acid monomer and a radically polymerizable acrylic monomer, and a copolymer containing a radically polymerizable monomer other than a radically polymerizable carboxylic acid monomer and a radically polymerizable acrylic monomer. Examples of the radically polymerizable carboxylic acid monomer include acrylic acid, methacrylic acid, and crotonic acid; monoesters and monoamides of dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, and itaconic acid; maleic anhydride, citraconic anhydride, and itaconic anhydride; and esters of vinyl alcohol and saturated carboxylic acids having 2 to 18 carbon atoms such as acetic acid, propionic acid, lauric acid, and stearic acid. Examples of the radical polymerizable acrylic monomer include alcohol esters of acrylic acid or methacrylic acid such as methyl, ethyl, propyl, butyl, and pentyl alcohol, and diesters such as ethylene glycol and propylene glycol. Examples of the radical polymerizable monomer (c) other than the radical polymerizable carboxylic acid monomer and the radical polymerizable acrylic monomer include styrene and α-methylstyrene. Among these carboxyl group-containing acrylic resins, copolymers in which the carboxyl group is derived from a methacrylic acid monomer are preferred, and copolymers of methacrylic acid (MAA), methyl methacrylate (MMA), and butyl methacrylate (BMA) are more preferred.
[0104] The acid value of the carboxyl group-containing acrylic resin obtained by copolymerizing the above-mentioned monomers is preferably 2 to 20 mgKOH / g. It is more preferably 3 mgKOH / g or more, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less. If it is less than 2 mgKOH / g, compatibility with the cellulose resin is likely to be problematic, and if it is more than 20 mgKOH / g, the content resistance (surfactant resistance, alkali resistance) tends to be poor. The mass average molecular weight of the carboxyl group-containing acrylic resin is preferably 30,000 to 100,000, more preferably 35,000 or more, and even more preferably 40,000 or more, and more preferably 90,000 or less, and even more preferably 80,000 or less. If the weight average molecular weight is less than 30,000, blocking properties, adhesive properties, etc. tend to decrease, while if it exceeds 100,000, solubility and solubility with cellulose resins tend to decrease. The content of the carboxyl group-containing acrylic resin in the solids of the printing ink composition for shrink packaging of the present invention is preferably 10.0% by mass or more, more preferably 13.0% by mass or more, and even more preferably 14.0% by mass or more, and is preferably 40.0% by mass or less, more preferably 35.0% by mass or less, and even more preferably 30.0% by mass or less.
[0105] (cellulose resin) As the cellulose resin, cellulose acetate propionate resin, cellulose acetate butyrate resin, nitrocellulose resin, etc., which have been conventionally used in gravure ink compositions, can be used. From the viewpoint of improving surfactant resistance, alkali resistance, etc., cellulose acetate propionate resin and cellulose acetate butyrate resin are preferred. The cellulose resin in the printing ink composition for shrink packaging of the present invention satisfies the following condition 1: In the shrink packaging printing ink composition, the ratio of the solid mass of the carboxyl group-containing acrylic resin to the solid mass of the cellulose resin is 80 / 20 to 60 / 40 (solid mass of carboxyl group-containing acrylic resin / solid mass of cellulose resin), and preferably 75 / 25 to 65 / 35. If the solid mass ratio of the cellulose resin is more than 40, the content resistance (surfactant resistance, alkali resistance) tends to decrease, while if it is less than 20, blocking resistance and the like tend to decrease. The total content of the cellulose resins in the solid content of the shrink packaging printing ink composition of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0106] (Cellulose acetate propionate resin) As the cellulose acetate propionate resin, a known cellulose acetate propionate resin that has been conventionally used in gravure printing ink compositions can be used. Cellulose acetate propionate resin is obtained by triesterifying cellulose with acetic acid and propionic acid, followed by hydrolysis. Generally, commercially available cellulose acetate propionate resins have an acetyl group content of 0.6 to 2.5 wt %, a propionate group content of 42.0 to 46.0 wt %, and a hydroxyl group content of 1.8 to 5.0 wt %. Among these, it is preferable to use a low molecular weight resin in order to improve the biomass content. The content of the cellulose acetate propionate resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0107] (Cellulose acetate butyrate resin) The cellulose acetate propionate resin can be a resin that has been conventionally used in gravure printing ink compositions. Cellulose acetate butyrate resin is obtained by triesterifying cellulose with acetic acid and butyric acid, followed by hydrolysis. Generally, resins with 2 to 30% by weight of acetylation, 17 to 53% by weight of butyrylation, and 1 to 5% of hydroxyl groups are commercially available. Among these, it is preferable to use a low-molecular-weight resin in order to improve the biomass content. The content of the cellulose acetate butyrate resin in the solid content of the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0108] (nitrocellulose resin) The nitrocellulose resin may be any nitrocellulose resin that has been used in gravure printing ink compositions. Nitrocellulose resins are obtained by reacting natural cellulose with nitric acid to replace three hydroxyl groups in the six-membered ring of the anhydroglucopyranose group in the natural cellulose with nitric acid groups, resulting in a nitric acid ester. The nitrocellulose resin used in the present invention preferably has a nitrogen content of 10 to 13% and an average degree of polymerization of 35 to 90. Specific examples include SS1 / 2, SS1 / 4, SS1 / 8, TR1 / 16, and NCRS-2 (Korea CNC Ltd.). The nitrocellulose resin content of the solids in the printing ink composition for shrink packaging of the present invention is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, and even more preferably 11.0% by mass or less.
[0109] (rosin resin and its derivatives) The rosin-based resin and its derivatives can be arbitrarily selected from the rosins and their derivatives that can be used in the reverse printing described above. The acid value of the rosin resin and its derivatives is preferably 150 mgKOH / g or less. If it exceeds 150 mgKOH / g, the stability and content resistance (alkali resistance and surfactant resistance) of the ink composition may be reduced. From the viewpoint of even better content resistance, the acid value is more preferably 100 mgKOH / g or less, even more preferably 50 mgKOH / g or less, even more preferably 30 mgKOH / g or less, extremely preferably 20 mgKOH / g or less, and most preferably 10 mgKOH / g or less. The content of the rosin resin and its derivatives in the solids of the printing ink composition for shrink packaging of the present invention is preferably 3.0 to 20.0% by mass, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more, and more preferably 15.0% by mass or less, and even more preferably 10.0% by mass or less.
[0110] (Other resins) In the printing ink composition for shrink packaging of the present invention, other resins may be used in combination as resin components other than the carboxyl group-containing acrylic resin, cellulose resin, rosin resin and derivatives thereof, as necessary, within a range that does not impair the effects of the present invention. Other resins include polyurethane urea resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, polyamide resin, acrylic resin, ethylene-vinyl acetate copolymer resin, chlorinated olefin resin, alkyd resin, vinyl acetate resin, ketone resin, polybutyral resin, cyclized rubber resin, chlorinated rubber resin, petroleum resin, olefin resin, polyester resin, polylactic acid resin, etc. The acrylic resin having a phosphate group may or may not be contained.
[0111] (pigment) The printing ink composition for shrink packaging can contain the above pigment.
[0112] (plasticizer) As the plasticizer, dioctyl sebacate, fatty acid triglyceride, ethyl toluenesulfonamide, acetyl tributyl citrate, 2-ethylhexyl stearate, 2-ethylhexyl palmitate, etc., which have traditionally been used in gravure printing inks, and epoxidized vegetable oils can be used. Among these, epoxidized vegetable oils such as epoxidized soybean oil and epoxidized linseed oil are preferred from the standpoints of content resistance (surfactant resistance, alkali resistance) and biomass content. The content of the plasticizer is not particularly limited. For example, the content of the plasticizer in the shrink packaging printing ink composition is preferably 0.05% by mass or more, more preferably 0.5% by mass or more, and is preferably 5.0% by mass or less, more preferably 3.0% by mass or less. When the content of the plasticizer is within the above range, the resulting shrink packaging printing ink composition has improved content resistance (surfactant resistance, alkali resistance).
[0113] (amide compounds) Furthermore, it is preferable for the shrink packaging printing ink composition to contain an amide compound in order to further improve scratch resistance, adhesion to substrates, abrasion resistance, and content resistance (surfactant resistance and alkali resistance). Examples of amide compounds include palmitic acid amide, stearic acid amide, ethylene bisoleic acid amide, and hexamethylene bisoleic acid amide. These may be used alone or in combination. When an amide compound is added, it is preferably contained in an amount of 0.1 to 5.0% by mass in the shrink packaging printing ink composition. In particular, to achieve a balance between scratch resistance, adhesion to substrates, abrasion resistance, surfactant resistance, and alkali resistance, it is preferable to contain it in an amount of 0.1 to 4.0% by mass, and more preferably 0.3 to 2.5% by mass.
[0114] (Solvent component) As the solvent component used in the printing ink composition for shrink packaging to form the printed layer in the present invention, the solvents that can be used in the ink composition for reverse printing described above can be used. Among these solvent components, from an environmental perspective, it is preferable to use alcohol-based solvents and / or ester-based solvents, more preferably alcohol-based solvents and / or ester-based solvents having 1 to 4 carbon atoms. Furthermore, it is preferable to use alcohol-based solvents having 1 to 4 carbon atoms and ester-based solvents in a mass ratio of alcohol / ester solvent = 60 / 40 to 80 / 20, and more preferably 63 / 37 to 75 / 25. If the ester-based solvent is more than 40, it may attack shrinkable OPS (untreated shrinkable polystyrene film). Furthermore, if the ester-based solvent is less than 20, the solubility of the resin component tends to decrease.
[0115] (Other ingredients) The printing ink composition for shrink packaging of the present invention may further contain, as necessary, additives such as abrasion resistance enhancers, antiblocking agents, pigment dispersants, antistatic agents, lubricants, crosslinking agents, antifoaming agents, drying regulators, other plasticizers, tackifiers, adhesion improvers, leveling agents, antioxidants, etc. Among these, additives derived from biomass are particularly preferable. Preferred lubricants include polyethylene (PE) wax, polypropylene wax, PTFE-based wax, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, montan wax, carnauba wax, shellac wax, amide wax, organic polymers, beeswax, and mixed waxes thereof, with polyethylene wax and polypropylene wax being more preferred.
[0116] (Method for producing shrinkable printing ink composition) As a method for producing a shrink printing ink composition using these materials, the same method as the method for producing the reverse printing ink composition described above can be used.
[0117] (Printing method using shrink printing ink composition and laminate obtained thereby) Next, a method for obtaining a shrink print using the shrink printing ink composition will be described. The release primer composition is applied to a resin substrate for shrink printing to form a release primer layer. Subsequently, shrink printing is performed inline or offline using a conventional printing method with the release primer composition. The printing speed and drying temperature can be appropriately selected from known speeds and temperatures. The resin substrate may be the same as that used for reverse printing.
[0118] <<Printing on the paper base side of laminated paper>> The printing ink composition used for printing on the paper substrate side of laminated paper may be, for example, a water-based flexographic printing ink composition, which contains the above-mentioned pigment, a binder resin, and various additives.
[0119] <Binder resin> Usable binders are not particularly limited, as long as they are resins obtained by polymerizing monomers having unsaturated double bonds, which are used in conventional aqueous flexographic printing ink compositions, or resins obtained by the reaction of functional groups. Specific examples of suitable binder resins include water-soluble acrylic resins copolymerized with acrylic acid or methacrylic acid and their alkyl esters, or styrene as the main monomer component, water-soluble styrene-acrylic resins, water-soluble styrene-maleic acid resins, water-soluble styrene-acrylic-maleic acid resins, water-soluble polyurethane resins, and water-soluble polyester resins. The content of the binder resin in the aqueous flexographic printing ink composition is preferably 1 to 20 wt %.
[0120] (Solvent component) An aqueous medium can be used as the solvent component used in the aqueous flexographic printing ink composition for forming the printing layer of the present invention. The aqueous medium may be water or a mixture of water and a water-miscible solvent. Examples of the water-miscible solvent include lower alcohols, polyhydric alcohols, and alkyl ethers or alkyl esters thereof, specifically lower alcohols such as methanol, ethanol, normal propanol, and isopropanol, polyhydric alcohols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and glycerin, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monoacetate, diethylene glycol monomethyl ether, and dipropylene glycol monomethyl ether. (Other ingredients) In addition to the components described above, the aqueous flexographic printing ink composition of the present invention may contain various additives, such as a film-forming agent, a pigment dispersant or a pigment dispersing resin, an anti-blocking agent, a wetting agent, a viscosity adjuster, a pH adjuster, an anti-foaming agent, and a general surfactant, which may be appropriately selected and used as needed.
[0121] (Method for producing aqueous flexographic printing ink composition) A typical method for producing an aqueous flexographic printing ink composition using these materials involves mixing and kneading the pigment, binder resin, and aqueous medium, and then adding and mixing the additives, aqueous medium, and the remaining predetermined materials. (Printing method using aqueous flexographic printing ink composition and laminate obtained thereby) Next, a method for obtaining a printed matter using the aqueous flexographic printing ink composition will be described. The release primer composition is applied to a resin substrate to form a release primer layer, then an adhesive is applied, a paper substrate is laminated, and then flexographic printing is performed on the paper substrate using a normal printing method with the aqueous flexographic printing ink composition. The resin substrate may be made of the above-mentioned polyethylene (PE) or the like.
[0122] <<Ink composition containing a resin other than the above polyurethane resin as a binder resin>> The printed matter of the present invention may employ an ink composition containing a resin other than the above polyurethane resin as a binder resin for the printed layer. For example, ink compositions containing polyurethane resins other than those mentioned above, or various binder resins known to be used in inkjet ink compositions and / or offset ink compositions can be used. Furthermore, ink compositions that are cured by active energy rays such as ultraviolet rays or electron beams, or aqueous or oil-based ink compositions such as dry-solidifying or heat-curing types can also be used. Furthermore, preferred is an ink composition that can be used for one or more of various printing methods, such as reverse printing, front printing, shrink printing, and printing on the paper substrate side of laminated paper formed by applying an adhesive to a substrate film and bonding the paper substrate, etc. Furthermore, more preferred is an ink composition that is suitable for retort when used in a retort container.
[0123] <<Varnish composition layer>> In the printed matter of the present invention, a layer made of a varnish composition may be formed on the printed layer formed by the printing ink. This varnish composition may be a known one, such as a solvent-based varnish composition, or an ultraviolet-curable or electron beam-curable varnish composition. The layer of varnish composition may be of any thickness. [Example]
[0124] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass." The numerical values for the amounts of each material in the tables are also in "parts by mass." The release primer composition used in the examples and comparative examples is a mixture of 8 parts ethanol and 2 parts water by mass. The solvent for the release primer composition of the present invention is not limited to this mixture.
[0125] <Examples and Comparative Examples of Backside Printing Using a Polyethyleneimine Compound or the Above Polybutadiene-Based Compound> <Production Example of Polyurethane Resin Varnish (Biomass Polyurethane)> Into a four-necked flask equipped with a stirrer, a cooling pipe, and a nitrogen gas inlet pipe, 200 parts by mass of a polyester diol having a mass average molecular weight of 2,000 obtained from sebacic acid (derived from castor oil) / succinic acid (derived from plants) = 30 / 70 (mass ratio) and 1,3-propanediol (derived from plants), 17.6 parts by mass of isophorone diisocyanate, and 21.0 parts by mass of hydrogenated MDI were charged, and the reaction was carried out at 100 to 105 °C for 6 hours while introducing nitrogen gas. After cooling to near room temperature, 400 parts by mass of ethyl acetate and 171 parts by mass of isopropanol were added, then 8.2 parts by mass of isophoronediamine was added for chain extension, and further 0.35 parts by mass of monoethanolamine was added for reaction. Thereafter, 1.3 parts by mass of isophoronediamine and 0.6 parts by mass of diethylenetriamine were added to terminate the reaction, and a polyurethane resin varnish (solid content 30% by mass, amine value 6.4 mgKOH / g) was obtained.
[0126] <Production Example of Polyurethane Resin Varnish (Not Biomass Polyurethane)> Into a four-necked flask equipped with a stirrer, a cooling pipe, and a nitrogen gas inlet pipe, 100 parts by mass of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 2,000, 100 parts by mass of polypropylene glycol having a mass average molecular weight of 2,000, 17.6 parts by mass of isophorone diisocyanate, and 21.0 parts by mass of hydrogenated MDI were charged, and the reaction was carried out at 100 to 105 °C for 6 hours while introducing nitrogen gas. After cooling to near room temperature, 400 parts by mass of ethyl acetate and 171 parts by mass of isopropanol were added, then 8.2 parts by mass of isophoronediamine was added for chain extension, and further 0.35 parts by mass of monoethanolamine was added for reaction. Thereafter, 1.3 parts by mass of isophoronediamine and 0.6 parts by mass of diethylenetriamine were added to terminate the reaction, and a polyurethane resin varnish (solid content 30% by mass, amine value 6.4 mgKOH / g) was obtained.
[0127] <Polyurethane Resin Varnish Obtained by Using a Compound in Which the Amino Group of a Polyamine Compound is Ketiminated with a Ketone Compound> (Method of producing ketimine solution 1) 51 parts of isophoronediamine, 31.2 parts of N-(2-hydroxyethyl)ethylenediamine, and 174 parts of acetone were mixed and stirred at room temperature for 1 hour, to obtain Ketimine Solution 1. (Method of manufacturing polyurethane resin) A four-neck flask equipped with a stirrer, a condenser, and a nitrogen gas inlet tube was charged with 400 parts of 3-methyl-1,5-pentyleneadipate diol having a number average molecular weight of 4,000, 33.3 parts of isophorone diisocyanate, and 0.04 parts of tetrabutyl titanate, and the mixture was reacted at 90 to 100°C for 6 hours while introducing nitrogen gas. Next, 812 parts of propyl acetate and 203 parts of isopropanol were added, and the mixture was cooled to near room temperature. 32.29 parts of the above ketimine solution 1 was added and stirred for 20 minutes, and then 3 parts of water was added and stirred for 15 minutes to obtain a polyurethane resin varnish (solid content 30%) with a mass average molecular weight of 35,000 and an amine value of 6.5 mgKOH / g. <Vinyl chloride / vinyl acetate copolymer> Solvine TA-3, Nissin Chemical Industry Co., Ltd. <Rosin and its derivatives> Polymerized rosin: Acid value 160mgKOH / g
[0128] <Chlorinated polypropylene varnish> 40 parts by mass of chlorinated polypropylene (solid content 50%) with a chlorination degree of 40% and a mass average molecular weight of 100,000 and 60 parts by mass of methylcyclohexane were mixed and stirred to obtain a chlorinated polypropylene varnish with a solid content of 20%. <Silica particles> Average particle size: 4.5 μm <Polyethylene wax> Average particle size: 2.11μm <Fatty acid amide> Ethylenebisstearamide
[0129] <Production example of reverse printing ink composition> Ten parts by mass of pigment (CIPB15:4), 30 parts by mass of each polyurethane resin, and 3 parts by mass of vinyl chloride-vinyl acetate copolymer (Solvine TA-3) were kneaded using a paint conditioner from Red Devil, and then 2 parts by mass of chlorinated propylene varnish (20% solids), 0.5 parts by mass of polymerized rosin, 0.5 parts by mass of silica particles, 0.2 parts by mass of polyethylene wax, 0.2 parts by mass of ethylene bisstearamide, 51 parts by mass of solvent, and 2 parts by mass of water were added to obtain a printing ink composition for reverse printing.
[0130] (Resin substrate) P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) (Removal primer) Polyethyleneimine listed in Table 1 below (trade names: Epomin (SP-018, P-1000, P-3000) (Nippon Shokubai Co., Ltd.), trade name: Lupasol P (BASF)) Polybutadiene compound (trade name: Titabond T-180E, (solid content concentration 10% by mass), Nippon Soda Co., Ltd.)
[0131] [Table 1]
[0132] Number average molecular weight: SP-018 / Number average molecular weight (Mn) by boiling point elevation P-1000, P-3000 / Number average molecular weight (Mn) by viscosity method Mass average molecular weight: Mass average molecular weight (Mw) by GPC method Amine value: Measured by acid titration using a non-aqueous system Amine ratio: measured by NMR (13C)
[0133] (Reverse printing, lamination, and test results) <Dry lamination 1 (base film: normal film)> To obtain the following laminate structure 1, the polyethyleneimine and polybutadiene compounds shown in Table 1 were diluted to the extent shown in Table 2 below to form each release primer composition, which was then coated on the treated surface of P-2161#25 using a gravure printing machine under the following conditions and dried. The coating amounts (g / m) in Table 2 were used. 2 ) is the amount of polyethyleneimine and polybutadiene-based compound. Each reverse-printing printing ink composition was further diluted with a mixed solvent of n-propyl acetate / isopropanol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed on the surface of each polyethyleneimine layer or the polybutadiene-based compound layer using a gravure printing machine under the following conditions, followed by drying to obtain a printed product. An adhesive (Takelac A-969V / Takelac A-5, solid content 30% by mass) was applied on top of it, and VMCPP was then adhered using a dry laminating machine to create a laminated print with the following laminate structure 1.
[0134] <Dry Laminate 2 (Base film: transparent vapor deposition film)> Each polyethyleneimine or polybutadiene compound listed in Table 1 above was diluted as shown in Table 2 below to form each release primer composition on the treated surface of each type of transparent vapor-deposited PET or transparent vapor-deposited NY film, and the composition was then applied and dried using a gravure printing machine under the following conditions, so as to obtain the following laminate structure 2. 2 ) is the amount of polyethyleneimine or the polybutadiene compound. Each reverse printing ink composition was further diluted with a mixed solvent of n-propyl acetate / isopropanol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed on the surface of each polyethyleneimine layer or each polybutadiene compound layer using a gravure printing machine under the following conditions, followed by drying to obtain a printed product. An adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) was applied on top of it, and RXC-22#60 was then adhered using a dry laminating machine to create a laminated print of the following laminate structure 2.
[0135] <Extrusion Lamination 1> Each polyethyleneimine or polybutadiene compound listed in Table 1 above was diluted as shown in Table 2 below to form each release primer composition on the treated surface of various films of PET, NY, or transparent vapor-deposited PET or transparent vapor-deposited NY, and the resulting composition was applied and dried using a gravure printing machine under the following conditions, so as to obtain the following laminate structure 3. The coating amount (g / m) in Table 2 is 2 ) is the amount of polyethyleneimine or the polybutadiene compound. Each reverse printing ink composition was further diluted with a mixed solvent of n-propyl acetate / isopropanol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed on the surface of each polyethyleneimine layer or each polybutadiene compound layer using a gravure printing machine under the following conditions, followed by drying to obtain a printed product. An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminated print with the following laminate structure 3.
[0136] <Extrusion Lamination 2> Each polyethyleneimine or polybutadiene compound listed in Table 1 above was diluted as shown in Table 2 below to form the release primer composition, which was then applied to the treated surface of the OPP film and dried under the following conditions using a gravure printing machine. The application amounts (g / m) in Table 2 were 2 ) is the amount of polyethyleneimine or the polybutadiene compound. Each reverse printing ink composition was further diluted with a mixed solvent of n-propyl acetate / isopropanol = 80 / 20 and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed on the surface of each polyethyleneimine layer or each polybutadiene compound layer using a gravure printing machine under the following conditions, followed by drying to obtain a printed product. An AC agent (Epomin P-1000, solid content 0.7% by mass) was applied thereon, and molten polyethylene was further laminated thereon using an extrusion laminator to produce a laminated print of laminate structure 4 below.
[0137] (Application conditions for each detachment primer composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate (wet coating amount 6 g / m 2 degree) Drying temperature: 70℃
[0138] (Printing conditions for reverse printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Printing plate: Helio 175 line / inch (130°) solid plate Drying temperature: 5 5℃
[0139] [Table 2]
[0140] In the following Examples and Comparative Examples, the results for laminate structure 1 are shown in Table 3, the results for laminate structure 2 in Table 4, the results for laminate structure 3 in Table 5, and the results for laminate structure 4 in Table 6. Tables 3 to 7 only show examples in which each polyethyleneimine compound was used. In Tables 3 to 7, each polyethyleneimine compound was used in a coating amount of 0.1 g / m2 solids. 2 , 0.02g / m 2 , 0.18g / m 2 , 0.36g / m 2 Instead of applying the polybutadiene compound so that the solid content was 0.1 g / m 2 , 0.02g / m 2 , 0.18g / m 2 , 0.36g / m 2 The results were the same as those when SP-018, P-1000, and P-3000 were used in each table. Laminate structure 1 : P-2161#25 / each polyethyleneimine compound or the above polybutadiene compound / each reverse printing ink composition / adhesive (Takelac A-969V / Takelac A-5 solids content 30%) / VMCPP P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) Adhesive (Takelac A-969V / Takelac A-5): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) VMCPP: Aluminum-coated non-oriented polypropylene (Toray)
[0141] Laminate structure 2 : Transparent vapor-deposited PET or transparent vapor-deposited NY / each polyethyleneimine-based compound or the above polybutadiene-based compound / each reverse printing ink composition / adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) / RXC-22#60 Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent vapor deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) Adhesive (Takelac A-515 / Takelac A-50): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) RXC-22#60: Unstretched propylene film (Mitsui Chemicals Tocello Co., Ltd.)
[0142] Laminate structure 3 PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / each polyethyleneimine compound or the above polybutadiene compound / each reverse printing ink composition / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / molten polyethylene PET: Polyethylene terephthalate film E-5102#12 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Unitika) Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent vapor deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) AC agent (Takelac A-3210 / Takelac A-3072): solid content 7% by mass (Mitsui Chemicals) Molten polyethylene: Sumikasen L705, resin temperature 355°C (Sumitomo Chemical Co., Ltd.)
[0143] Laminate structure 4 OPP / each polyethyleneimine compound or the above polybutadiene compound / each reverse printing ink composition / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene OPP film: Corona-discharged biaxially oriented polypropylene film P-2161#25 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Toyobo Co., Ltd.) AC agent (Epomin P-1000): Polyethyleneimine, solid content 0.7% by mass (Nippon Shokubai Co., Ltd.) Molten polyethylene: Sumikasen L705, resin temperature 355°C (Sumitomo Chemical Co., Ltd.)
[0144] <Evaluation of ink release properties> After printing, 1.5 g of each of the above printed materials was thoroughly dried and then shredded into small pieces of approximately 15 mm MD x 25 mm TD to obtain samples for ink release test. (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of the water-based desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of the desorption solution 2 consisting of an alkaline aqueous solution) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0145] (detachment) After each release solution reached 70°C, the ink release test samples were placed in Release Solution 1 (water) and Release Solution 2 (alkaline aqueous solution), respectively, and stirred using a 25mm stainless steel stirring blade for 60 minutes for Release Solution 1 (water), and for 30 minutes for Release Solution 2 (alkaline aqueous solution). After stirring, the HDPE (high-density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solutions and the various film pieces were separated using a stainless steel mesh with approximately 2mm openings. (rinse) After removal, the various films were transferred to a 200 cc HDPE container and 100 g of water was added. The film pieces were then stirred for 5 minutes using a 25mm diameter stainless steel stirring blade. After leaving the film pieces to stand for 5 minutes, the film pieces were separated from the water using a stainless steel mesh. After drying, the film pieces were visually evaluated for ink releasability from the films.
[0146] Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria for laminate structures 1 to 4) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled
[0147] Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria for laminate structures 1 to 4) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled
[0148] Tape adhesive strength (for each printed item immediately after printing and drying) Using a gravure printer, each of the polyethyleneimines was diluted as shown in Tables 3 to 6 below to obtain a predetermined coating amount on the treated surface of each film, and each release primer composition was applied and dried using the gravure printer under the conditions described below. Each reverse printing ink composition was further diluted by adding a normal propyl acetate / isopropanol = 80 / 20 mixed solvent to the surface of each release primer composition layer to give a dilution of 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and then printed and dried using the gravure printer under the conditions described above to obtain each printed product. Adhesion was evaluated according to the following criteria based on the degree of peeling of the printed film when cellophane tape was applied to the printed surface of each of the obtained prints and then quickly peeled off. (Evaluation Criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0149] Laminate Strength After each laminate print of Laminate Configurations 1 to 4 was obtained, it was cut into a width of 15 mm, and the T-peel strength was measured using a peel tester manufactured by Yasuda Seiki Seisakusho. (Evaluation criteria for laminate structures 1 and 4) ○: Peel strength is 1.2N / 15mm or more △: Peel strength is 0.7N / 15mm or more and less than 1.2N / 15mm ×: Peel strength is less than 0.7N / 15mm (Evaluation criteria for laminate structure 2 and 3) ○: Peel strength is 5N / 15mm or more △: Peel strength is 3N / 15mm or more and less than 5N / 15mm ×: Peel strength is less than 3N / 15mm
[0150] Blocking property Using a gravure printer, each release primer composition prepared by diluting the polyethyleneimine or polybutadiene compound as shown in Table 3 below was applied to the treated surface of each film under the following conditions to obtain a predetermined coating amount, followed by drying. Each reverse printing ink composition was further diluted with a normal propyl acetate / isopropanol = 80 / 20 mixed solvent and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and printed and dried under the following conditions on the surface of each release primer composition layer. The printed surface of each printed matter and the untreated surface of each film were then combined, and a coating of 400 g / cm was applied. 2 After leaving the film at 40°C for 12 hours under a load of 1.0 g, the blocking resistance was evaluated based on the state of each film when peeled off. (Evaluation criteria) ○: Peels off without resistance and there is no transfer of the ink film △: There is resistance, but the ink film does not transfer at all ×: Transfer of ink film was observed
[0151] The following evaluations were the same for all reverse printing ink compositions using three types of polyurethane resin varnish (polyurethane resin varnish (biomass polyurethane), polyurethane resin varnish (non-biomass polyurethane), and polyurethane resin varnish obtained using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound). Therefore, the results for polyurethane resin varnish (biomass polyurethane) are shown below.
[0152] [Table 3]
[0153] [Table 4]
[0154] [Table 5]
[0155] [Table 6]
[0156] <Comparative example: Dry laminate 1 (base film: normal film)> Each comparative release primer composition was diluted to a predetermined coating amount and applied to the treated surface of each film, and then dried using a gravure printer under the following conditions, so as to obtain the following comparative laminate structure 1. Each reverse printing ink composition was diluted by adding an 80 / 20 mixed solvent of n-propyl acetate / isopropanol to the surface of each release primer composition layer to give a dilution of 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and then printed and dried using a gravure printer under the following conditions to obtain a printed product. An adhesive (Takelac A-969V / Takelac A-5, 30% solids) was applied on top of it, and VMCPP was then adhered using a dry laminating machine to create a laminated print with the following laminate structure 1.
[0157] <Comparative example dry laminate 2 (substrate film: transparent vapor-deposited film)> Each comparative release primer composition was diluted to a specified coating amount onto the treated surface of various transparent vapor-deposited PET or transparent vapor-deposited NY films, and then coated and dried using a gravure printing machine under the conditions below to obtain printed matter, so as to form the following laminate structure 2. Each diluted ink composition was then diluted with an 80 / 20 mixed solvent of n-propyl acetate / isopropanol to a viscosity of 16 seconds using a Rigo Zahn Cup No. 3. This diluted ink composition was then printed and dried using a gravure printing machine under the conditions below to obtain printed matter. An adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) was applied on top of it, and RXC-22#60 was then adhered using a dry laminating machine to create a laminated print of the following laminate structure 2.
[0158] <Extrusion Laminate 1 of Comparative Example> Each comparative release primer composition was diluted to a specified coating amount onto the treated surface of various films (PET, NY, transparent vapor-deposited PET, or transparent vapor-deposited NY) to obtain the following laminate structure 3, and then coated and dried using a gravure printing machine under the following conditions to obtain a print. Each diluted ink composition was then diluted with an 80 / 20 mixed solvent of n-propyl acetate / isopropanol to a viscosity of 16 seconds using a Rigo Zahn Cup No. 3. This diluted ink composition was then printed and dried using a gravure printing machine under the following conditions to obtain a print. An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminated print with the following laminate structure 3.
[0159] <Extrusion Laminate 2 of Comparative Example> Each comparative example of a release primer composition was diluted to a predetermined application amount onto the treated surface of an OPP film so as to form the following laminate structure 4, and then coated and dried using a gravure printing machine under the following conditions to obtain a print: Each reverse-printing printing ink composition was further diluted with a normal propyl acetate / isopropanol = 80 / 20 mixed solvent and diluted to 16 seconds using a Zahn Cup No. 3 manufactured by Rigo Co., Ltd., and then printed and dried using a gravure printing machine under the following conditions to obtain a print: An AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) was applied on top of it, and molten polyethylene was then laminated on top of it using an extrusion laminator to create a laminated print with the following laminate structure 4.
[0160] (Application methods and conditions for each release primer composition in comparative examples) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃
[0161] (Printing method and conditions for reverse printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃
[0162] Comparative Example Laminate Structure 1: P-2161#25 / Comparative Example Detachable Primer Composition / Reverse Printing Ink Composition / Adhesive (Takelac A-969V / Takelac A-5 30% solids) / VMCPP P-2161#25: Biaxially oriented polypropylene film (thickness 25 μm) (Toyobo Co., Ltd.) Adhesive (Takelac A-969V / Takelac A-5): Aromatic ether-based two-component adhesive, solid content 30% by mass (Mitsui Chemicals) VMCPP: Aluminum-coated non-oriented polypropylene (Toray)
[0163] Comparative example laminate structure 2 Transparent vapor-deposited PET or transparent vapor-deposited NY / each comparative release primer composition / each reverse printing ink composition / adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) / RXC-22#60 PP Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent vapor deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) Adhesive (Takelac A-515 / Takelac A-50): Two-component adhesive, solid content 30% by mass (Mitsui Chemicals) RXC-22#60: Unstretched propylene film (Mitsui Chemicals Tocello Co., Ltd.)
[0164] Comparative example laminate structure 3 PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / each comparative example's release primer composition / each reverse printing ink composition / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / melt polyethylene PET: Polyethylene terephthalate film E-5102#12 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Unitika) Vapor-deposited PET: GL-ARH-F (Toppan Printing Co., Ltd.) Transparent vapor deposition NY: GL-ARH-W (Toppan Printing Co., Ltd.) AC agent (Takelac A-3210 / Takelac A-3072): solid content 7% by mass (Mitsui Chemicals) Molten polyethylene: Sumikasen L705, resin temperature 355°C (Sumitomo Chemical Co., Ltd.)
[0165] Comparative example laminate structure 4 OPP / each comparative release primer composition / each reverse printing ink composition / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene OPP film: Corona-discharged biaxially oriented polypropylene film P-2161#25 (Toyobo Co., Ltd.) NY: Nylon film ON-15#12 (Toyobo Co., Ltd.) AC agent (Epomin P-1000): Polyethyleneimine, solid content 0.7% by mass (Nippon Shokubai Co., Ltd.) Molten polyethylene: Sumikasen L705, resin temperature 355°C (Sumitomo Chemical Co., Ltd.) (Each of the comparative release primer compositions) PVA: Poval 28-98 (polyvinyl alcohol with a saponification degree of 90% or more) (Kuraray Co., Ltd.) General-purpose polyurethane: the polyurethane resin varnish described above (not biomass polyurethane)
[0166] The following evaluations were the same for all reverse printing ink compositions using three types of polyurethane resin varnish (polyurethane resin varnish (biomass polyurethane), polyurethane resin varnish (non-biomass polyurethane), and polyurethane resin varnish obtained using a compound in which the amino group of a polyamine compound is ketiminated with a ketone compound). Therefore, the results for polyurethane resin varnish (biomass polyurethane) are shown below. The ink release property, adhesiveness and lamination strength were evaluated by the same methods and criteria as above. However, the ink releasability was carried out with an alkaline aqueous solution of the release liquid 2. As the release liquid 2 composed of an alkaline aqueous solution, 2 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, stirred and dissolved to use a release liquid composed of an alkaline aqueous solution.
[0167] All of the laminate structures 1 to 4 of the comparative examples had the same results. Therefore, the results regarding the laminate structure 1 are shown in Table 7 below.
[0168]
Table 7
[0169] When the primer composition for release of the present invention was applied, it could be smoothly released by either water or an alkaline aqueous solution. And it was also excellent in the adhesiveness immediately after printing, the laminate strength, and the blocking resistance. However, according to the results shown in Tables 3 to 7, when the primer composition for release of the present invention was not applied, and when PVA and general-purpose polyurethane were applied, it was impossible to achieve both excellent releasability and laminate strength.
[0170] <Example of surface printing using a polyethyleneimine compound or the above polybutadiene-based compound> (Polyurethane resin varnish) A four-neck flask equipped with a stirrer, a condenser, and a nitrogen gas inlet tube was charged with 100 parts by weight of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 2,000, 100 parts by weight of polypropylene glycol having a mass average molecular weight of 2,000, 17.6 parts by weight of isophorone diisocyanate, and 21.0 parts by weight of hydrogenated MDI, and the mixture was allowed to react for 6 hours at 100 to 105 ° C. while introducing nitrogen gas. After cooling to near room temperature, 523.3 parts by weight of ethyl acetate and 223.8 parts by weight of isopropanol were added, followed by the addition of 8.2 parts by weight of isophorone diamine to extend the chain, and then 0.35 parts by weight of monoethanolamine was added to allow the reaction to proceed. Then, 1.3 parts by weight of isophorone diamine and 0.6 parts by weight of diethylene triamine were added to terminate the reaction, and a urethane resin (polyurethane resin varnish (solids content 25% by weight)) was obtained.
[0171] (CAB) Cellulose acetate butyrate (Eastman Chemical Company, number average molecular weight 70,000, butyryl content 35-39%)
[0172] (nitrocellulose) 35 parts by mass of nitrocellulose (hydrated with 30% by weight of water) (NOBEL NC CO., Ltd. DLX5-8) was dissolved in a mixed solvent consisting of 58 parts of ethyl acetate and 7 parts of isopropanol to obtain a nitrocellulose solution with a solid content of 35% by mass.
[0173] (Polyamide resin) Thermoplastic polyamide resin (Mw 8,000, acid value 2, softening point 110°C) made from tall oil fatty acid as a reaction raw material (Polyvinyl chloride) Solvine TA5R (Nissin Chemical Industry Co., Ltd.) (acrylic resin) Hiros-X RL-4032 (solid content 40% by mass) (Seiko PMC Co., Ltd.) (polyethylene wax) PA-60 (solid content 25% by mass) (Polycon Corporation) (Titanium oxide) Typec PFR209 (Ishihara Sangyosha)
[0174] <Preparation of printing ink composition> A printing ink composition was prepared by kneading each material in a paint conditioner according to the mass ratio (mass%) in Table 8 below. The resulting printing ink composition was then subjected to gravure printing under the following conditions to obtain a printed matter. The resulting printed matter was evaluated for adhesion and releasability according to the following evaluation methods.
[0175] <Creating printed materials> The release primer (polyethyleneimine P-1000) or the polybutadiene compound was diluted to a specified coating weight onto a corona-discharge-treated stretched polypropylene film (product name OPP P-2161, 25 μm, Toyobo Co., Ltd.) and then dried using a gravure press under the following conditions. Each diluted surface-printing ink composition listed in Table 8 below was added to a corresponding mixed solvent and diluted to a 16-second run in a Rigo Zahn Cup No. 3. The diluted surface-printing ink composition was printed and dried using a gravure press under the following conditions to obtain a surface-printing ink composition print. 1.5 g of each surface-printing ink composition print was shredded into small pieces approximately 15 mm MD x 25 mm TD to obtain samples for printing layer peeling tests.
[0176] (Removal primer composition application method and application conditions) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃ (Printing method and conditions for surface printing ink composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃ The ink release property and adhesion were evaluated by the same method and criteria as described above.
[0177] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree of peeling of the printed film when cellophane tape was applied to the printed surface of each printed product obtained in the production of the prints and then quickly peeled off. Hereinafter, the evaluation of adhesion in this specification was based on this evaluation.
[0178] (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film. <Printing layer peeling test method>
[0179] (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution.
[0180] (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (detachment) After the temperature of each release solution reached 70°C, the above-mentioned print layer peeling test samples were placed in the release solution and stirred using a 25mm stainless steel stirring blade for 60 minutes for release solution 1 (water) or 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE (high-density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and film pieces were separated using a stainless steel mesh with approximately 2mm openings. (rinse) After the film was removed, it was transferred to a 200cc HDPE container and 100g of water was added. The mixture was stirred for 5 minutes using a stainless steel stirring blade with a blade diameter of 25mm. After leaving the mixture to stand for 5 minutes, the film pieces were separated from the water using a stainless steel mesh. After the film pieces were dried, the releasability of the ink from the film was visually evaluated.
[0181] Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled
[0182] Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled
[0183] [Table 8]
[0184] [Table 9]
[0185] Desorption primer composition in Table 9: When polyethyleneimine P-1000 was applied, in any of the surface printing ink compositions 1 to 8, desorption was possible using water or an alkaline aqueous solution as the desorption liquid, and the adhesion to corona-discharge-treated stretched polypropylene film (product name OPP P-2161, 25 μm, Toyobo Co., Ltd.) was also good. In Table 9, instead of applying each polyethyleneimine-based compound so that the coating amount of the solid content was 0.18 g / m 2 Examples were also carried out in which the above polybutadiene-based compound was applied so that the coating amount of the solid content was 0.02 g / m 2 , 0.18 g / m 2 . All of the results were the same as those when carried out with P-1000 in Table 9 at 0.18 g / m 2 .
[0186] <Examples of shrink printing using a polyethyleneimine compound or the above polybutadiene-based compound> (Synthesis of acrylic resin) After polymerization by solution polymerization with a monomer composition [n-butyl methacrylate / n-butyl acrylate / 2-hydroxyethyl methacrylate / methyl methacrylate = 35 / 20 / 15 / 30 (mass ratio)], the one obtained by evaporating the solvent was used. The mass average molecular weight was 60,000 and the hydroxyl value was 60 mgKOH / g.
[0187] (Production of shrink packaging printing ink composition 1) 10.0 parts by mass of pigment (C.I.PB15:4), 10.0 parts by mass of the above acrylic resin, 3.5 parts by mass of nitrocellulose (product name: LIG 1 / 8, SNPE Japan Co., Ltd.), 20.0 parts by mass of methylcyclohexane, 35.5 parts by mass of isopropanol, 21.0 parts by mass of ethyl acetate, were kneaded and dispersed by a conventional method to produce shrink packaging printing ink composition 1.
[0188] (Production of shrink packaging printing ink composition 2) 10.0 parts by mass of pigment (CIPB15:4), 9.0 parts by mass of carboxyl group-containing acrylic resin (monomer composition: MAA / MMA / BMA, theoretical acid value 3 mgKOH / g, mass average molecular weight 60,000), 10.0 parts by mass of isopropanol, and 15.0 parts by mass of ethyl acetate were kneaded using a paint conditioner, and a paint containing 1.2 parts by mass of the carboxyl group-containing acrylic resin, 5.0 parts by mass of cellulose acetate butyrate (CAB-381-0.5, Eastman Chemical Company, number average molecular weight 30,000), 5.0 parts by mass of rosin ester (acid value 7 mgKOH / g), 1.0 part by mass of epoxidized soybean oil, 0.5 parts by mass of stearic acid amide, and Spray 2.2 parts by mass of 30 (Sasol), 0.3 parts by mass of BYK-094 (BYK), 4.5 parts by mass of normal propanol, 27.4 parts by mass of isopropanol, and 9.1 parts by mass of ethyl acetate were added and mixed to prepare printing ink composition 2 for shrink packaging.
[0189] (Production of printed matter) The above-mentioned release primer composition (polyethyleneimine P-1000 or the above-mentioned polybutadiene-based compound) diluted to a specified coating amount was applied to a crystallizable shrinkable PET (polyethylene terephthalate) film and dried using a gravure printer under the following conditions. Each of the above-mentioned shrink packaging printing ink compositions was added to each mixed solvent and diluted to 16 seconds in a Rigosha Zahn Cup No. 3. Each diluted shrink packaging printing ink was printed on the surface of each polyethyleneimine film using a gravure printer under the following conditions and dried to obtain each printed product. 1.5 g of each shrink packaging printing ink composition print was shredded into small pieces approximately 15 mm MD x 25 mm TD to obtain samples for printing layer peeling tests. (Removal primer composition application method and application conditions) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃ (Printing method and conditions for printing ink composition for shrink packaging) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 55℃
[0190] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each printed product obtained in the production of the printed product and then quickly peeled off. (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0191] <Printing layer peeling test method> (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution.
[0192] (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred using a 25mm stainless steel stirring blade for 60 minutes for release solution 1 (water) or 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and PET (polyethylene terephthalate) film pieces were separated using a stainless steel mesh with approximately 2mm openings. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled Desorption (hot water) conditions: Stirring in 70°C hot water for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the film as film pieces. ×: Not peeled
[0193] [Table 10]
[0194] According to Table 10, when polyethyleneimine P-1000 was applied, release was possible even when water or an alkaline aqueous solution was used as the release liquid, and the adhesion to the crystallizable shrinkable PET film was also good in both shrink packaging printing ink compositions 1 and 2. In Table 10, when each polyethyleneimine compound was applied in a solids amount of 0.18 g / m 2 Instead of applying the polybutadiene compound so that the solid content was 0.02 g / m 2 , 0.18g / m 2 All of these results were obtained using the P-1000 coating in Table 9 at 0.18 g / m 2 As can be seen, the results were the same as when P-1000 was used in Table 10.
[0195] <Example of printing on the paper base material side of laminated paper using a polyethyleneimine compound or the above polybutadiene-based compound> (Manufacture of printing ink composition for aqueous flexo) <Manufacturing method of aqueous printing ink> 15 parts by mass of pigment (C.I.PB15:3), 15 parts by mass of alkali-soluble water-soluble resin (Joncryl HPD-671, BASF, solid content 25%), 0.5 parts by mass of (ethylene oxide / propylene oxide) block polymer ((EO / PO) block polymer, HLB value 14, Mw16000), 0.03 parts by mass of dibutyl glycol, and 22.97 parts by mass of water were kneaded and dispersed in a bead mill, and then 43.25 parts by mass of styrene-acrylic resin emulsion (acid value 38 mgKOH / g, glass transition temperature 9°C, solid content 38.5%), 2.5 parts by mass of polyethylene wax (Chemipar W-100, solid content 35% by mass, Mitsui Chemicals), and 0.75 parts by mass of defoaming agent (SN Deformer 777#C, San Nopco) were added and mixed to obtain an aqueous flexo printing ink composition.
[0196] (Production of printed matter) Each desorption primer composition diluted as shown in Table 2 below with each polyethyleneimine or the above polybutadiene-based compound described in Table 1 above was applied and dried on a linear low-density polyethylene film (TUX-HC#50, thickness 25 μm, Mitsui Chemicals Toho Cellulose Co., Ltd.) under the following conditions using a gravure printing machine. An adhesive (Takelac A-969V / Takelac A-5, solid content 30% by mass) was applied thereon, and then thick paper satin-finish kraft paper (OK Blizzard, 770 g / m 2 , Oji Materia Co., Ltd.) was adhered to obtain the laminated paper of the present invention. The above flexo printing ink composition was developed on the surface of this paper using a 200-line hand proofing machine and dried to obtain a printed matter. 1.5 g of each of these printed matters was cut into small pieces of about MD15 mm × TD25 mm to obtain samples for the printing layer peeling test. (Method and conditions for applying desorption primer composition) Coating machine: Gravure printing machine Coating speed: 100 m / min Plate: Helio 175 line / inch (130°) solid plate Drying temperature: 70℃
[0197] Laminate Construction: TUX-HC#50 / polyethyleneimine or the above polybutadiene compounds / adhesive (Takelac A-969V / Takelac A-5 solids 30%) / OK Blizzard (70g / m 2 ) / Flexographic printing ink composition
[0198] <Printing layer peeling test method> (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0199] (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred using a 25mm stainless steel stirring blade for 60 minutes for release solution 1 (water) or 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and PET (polyethylene terephthalate) film pieces were separated using a stainless steel mesh with approximately 2mm openings. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: Paper was completely peeled off from the film as a piece of film ×: Not peeled Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: Paper was completely peeled off from the film as a piece of film ×: Not peeled
[0200] Laminate Strength Each of the printed materials was cut into a width of 15 mm, and the T-peel strength was measured using a peel tester manufactured by Yasuda Seiki Seisakusho Co., Ltd. Hereinafter, the evaluation of adhesiveness in this specification was carried out based on this evaluation. (Laminate Structure 1 Evaluation Criteria) ○: Peel strength is 1.2N / 15mm or more △: Peel strength is 0.7N / 15mm or more and less than 1.2N / 15mm ×: Peel strength is less than 0.7N / 15mm
[0201] The evaluation results are shown in Table 11 below.
[0202] [Table 11]
[0203] As shown in Table 11, when the detachment primer composition of the present invention using a polyethyleneimine compound was applied, smooth detachment was achieved with both water and an alkaline aqueous solution. Furthermore, the laminate strength after printing was excellent. In Table 11, when each polyethyleneimine compound was applied in an amount of 0.1 g / m2 as a solid component, 2 , 0.02g / m 2 , 0.18g / m 2 , 0.36g / m 2 Instead of applying the polybutadiene compound so that the solid content was 0.1 g / m 2 , 0.02g / m 2 , 0.18g / m 2 , 0.36g / m 2Examples of coating were also carried out so that there were four cases. The results were the same as those when SP-018, P-1000, and P-3000 were adopted in each table. However, according to the results shown in Table 11, when the primer composition for desorption of the present invention was not applied, it was impossible to achieve both excellent desorbability and laminate strength.
[0204] <B. Examples and Comparative Examples Using a Mixture Containing a Polyethyleneimine Compound and a Glycidyl Group-containing Silane Coupling Agent and / or an Isocyanate Group-containing Silane Coupling Agent> Next, the case of using a primer composition when a silane coupling agent is contained in a polyethyleneimine-based compound will be described. In the primer composition of the present invention, from the viewpoint of improving adhesiveness, a silane coupling agent containing a glycidyl group and a silane coupling agent containing an isocyanate group can be contained. Examples of the silane coupling agent containing a glycidyl group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethoxydimethoxysilane, 3-glycidoxypropylmethoxydiethoxysilane, 3-glycidoxypropyltriethoxysilane, and the like. Examples of the silane coupling agent containing an isocyanate group include triethoxy(3-isocyanatopropyl)silane and the like. The silane coupling agent containing a glycidyl group and the silane coupling agent containing an isocyanate group are preferably blended so that the ratio of (the number of glycidyl groups + the number of isocyanate groups of the silane coupling agent) to the number of amino groups of the polyethyleneimine-based compound, that is, ((the number of glycidyl groups of the silane coupling agent + the number of isocyanate groups of the silane coupling agent) / the total number of primary amino groups and secondary amino groups of the polyethyleneimine-based compound) is 0.20 to 2.50. And 0.30 or more is more preferable, 0.50 or more is still more preferable, 2.20 or less is more preferable, and 1.90 or less is still more preferable. The number of amino groups is the total number of the number of each of the primary amino groups and the secondary amino groups. This ratio of (number of glycidyl groups in the silane coupling agent + number of isocyanate groups in the silane coupling agent) / total number of primary amino groups and number of secondary amino groups in the polyethyleneimine compound can be calculated using the following formula. [(Glycidyl group-containing silane coupling agent application amount (g / m 2 ) × average number of glycidyl groups per molecule) / average molecular weight of glycidyl group-containing silane coupling agent (g / mmol)] + [(coating amount of isocyanate group-containing silane coupling agent (g / m 2 ) × average number of isocyanate groups in one molecule / average molecular weight of isocyanate group-containing silane coupling agent (g / mmol)], [(coating amount of polyethyleneimine compound (g / m 2 ) × amine value (mmol / g) × (average number of primary amino groups + number of secondary amino groups per molecule) / (average number of primary amino groups + number of secondary amino groups + number of tertiary amino groups per molecule)).
[0205] <Removable primer layer> Each release primer composition having the solids concentration shown in Table 12 below was applied and dried using a gravure printing machine under the following conditions to achieve the coating amount shown in Table 13. The coating amount of each component of the release primer composition for each Example in Table 13 is the amount of solids of each component contained in the coating layer per unit area. The solids concentration of each release primer composition is such that, when formed into a coating layer, it becomes a polyethyleneimine-based compound in the coating layer, and that a silane coupling agent having a glycidyl group, such as 3-glycidyloxypropyltrimethoxysilane or 3-glycidyloxypropyltriethoxysilane, and a silane coupling agent having an isocyanate group, such as triethoxy(3-isocyanatopropyl)silane, is contained in the respective coating amounts. For example, Example B1 contains a mixture of a polyethyleneimine-based compound P-1000 and a silane coupling agent having a glycidyl group in the release primer. As a result of applying this release primer, the amount of the component derived from the polyethyleneimine compound of P-1000 applied was 0.02 g / m 2and the coating amount of the component derived from the silane coupling agent having a glycidyl group is 0.02 g / m 2 Furthermore, the ratio of the number of glycidyl groups in the silane coupling agent or the number of glycidyl groups and / or the number of isocyanate groups in the isocyanate group-containing silane coupling agent to the number of amino groups in the polyethyleneimine compound in Table 13 is determined based on the above-mentioned concept, and is the value obtained by dividing the number of glycidyl groups or the number of isocyanate groups in the applied detachment primer composition by the total number of the primary amino groups and the secondary amino groups.
[0206] (Application conditions for each detachment primer composition) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate (wet coating amount 6 g / m 2 degree) Drying temperature: 70℃
[0207] When printing with a gravure printer, the solid mass % of the release primer is diluted as shown below, and when printing with a gravure printer under the container conditions, the following application amount (g / m 2 )
[0208] [Table 12]
[0209] [Table 13]
[0210] Examples and comparative examples of printing formats using a primer composition for desorption containing a silane coupling agent, which uses a mixture of the B. polyethyleneimine compound of the present invention and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent, will be described in the order of printing on the reverse side printing, front side printing, shrink printing, a base material film, and the paper base material side of a laminated paper obtained by applying an adhesive and bonding a paper base material. Regarding the printing formats using a primer composition for desorption that does not contain the silane coupling agent described above: For the same parts of the examples and comparative examples of reverse side printing, front side printing, shrink printing, a base material film, and printing on the paper base material side of a laminated paper obtained by applying an adhesive and bonding a paper base material, they will be omitted.
[0211] <Examples and Comparative Examples of Reverse Side Printing Using a Mixture of a B. Polyethyleneimine Compound and a Glycidyl Group-Containing Silane Coupling Agent and / or an Isocyanate Group-Containing Silane Coupling Agent> (Dry Lamination) · Lamination Structure 1 : P-2161#25 / each silane coupling agent + each polyethyleneimine / each reverse side printing ink composition / adhesive (Takelac A-969V / Takelac A-5 solid content 30%) / VMCPP · Lamination Structure 2 : Transparent vapor-deposited PET or transparent vapor-deposited NY / each silane coupling agent + each polyethyleneimine / each reverse side printing ink composition / adhesive (Takelac A-515 / Takelac A-50, solid content 30% by mass) solid content 30%) / RXC-22#60 (extrusion lamination) · Lamination Structure 3 : PET or NY or transparent vapor-deposited PET or transparent vapor-deposited NY / each silane coupling agent + each polyethyleneimine / each reverse side printing ink composition / AC agent (Takelac A-3210 / Takelac A-3072, solid content 7% by mass) / molten polyethylene · Lamination Structure 4 OPP / each silane coupling agent + each polyethyleneimine / each reverse printing ink composition / AC agent (Epomin P-1000, solid content 0.7% by mass) / molten polyethylene
[0212] <Deinking (evaluation of ink release properties)> Deinking (evaluation of ink release properties) was carried out as follows. After printing, 1.5 g of each of the above printed materials was thoroughly dried and then shredded into small pieces of approximately 15 mm MD x 25 mm TD to obtain samples for ink release test. (Preparation of the release solution consisting of an alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid consisting of an alkaline aqueous solution. (Preheating of the desorption solution consisting of an alkaline aqueous solution) 100 g of the release solution consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (detachment) After each release solution reached 70°C, the ink release test samples were placed in the respective alkaline aqueous solution release solutions, and the alkaline aqueous solution release solutions were stirred for 30 minutes using a 25mm diameter stainless steel stirring blade. After stirring, the HDPE (high-density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solutions and the various film pieces were separated using a stainless steel mesh with approximately 2mm openings. (rinse) After removal, the various films were transferred to a 200cc HDPE container and 100g of water was added. The mixture was stirred for 5 minutes using a stainless steel stirring blade with a blade diameter of 25mm. After leaving the mixture to stand for 5 minutes, the various film pieces were separated from the water using a stainless steel mesh. After drying the various film pieces, the releasability of the ink from the various films was visually evaluated. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: Ink film did not peel off from the resin substrate film as a film piece · For laminating structures 1 to 4, the results were the same as shown in Table 14
[0213]
Table 14
[0214] <B. Examples of surface printing using a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> Evaluation was carried out in the same manner as in the example of surface printing without using the above silane coupling agent, except that the primer for peeling was changed to each primer composition for peeling containing the above silane coupling agent · For surface printing ink compositions 1 to 8, the results were the same as shown in Table 15
[0215]
Table 15
[0216] <B. Examples of shrink printing using a mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> Evaluation was carried out in the same manner as in the example of shrink printing without using the above silane coupling agent, except that the primer composition for peeling was changed to each primer composition for peeling containing the above silane coupling agent · For shrink packaging printing ink compositions 1 and 2, the results were the same as shown in Table 16
[0217]
Table 16
[0218] <Example of printing on the paper base material side of laminated paper using a mixture containing a polyethyleneimine compound, a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent> The primer composition for release was evaluated in the same manner as in the example of printing on the paper base material of laminated paper without using the above silane coupling agent, except that each primer composition for release containing the above silane coupling agent was changed. The evaluation results are shown in Table 17.
[0219]
Table 17
[0220] <Examples and Comparative Examples Using a Siloxane-Modified Polyethyleneimine Compound or the Above Polybutadiene Compound> Next, the case of using the primer composition for release when containing a siloxane-modified polyethyleneimine compound or the above polybutadiene compound will be described. In the primer composition for release of the present invention, from the viewpoint of adhesiveness, a siloxane-modified polyethyleneimine compound or the above polybutadiene compound can be contained. As the siloxane-modified polyethyleneimine compound, a siloxane-modified polyethyleneimine compound obtained by the reaction of a component containing polyethyleneimine and at least one amine-reactive hydrolyzable organosilane represented by the formula: R-Z-SiY3 [wherein, R represents an amine-reactive group selected from the group consisting of an isocyanate group, an oxiranyl group, a glycidoxy group, an acryloxy group, a carbethoxy group, a carbomethoxy group, a vinylsulfonyl group, and an acrylamide group, Z represents a divalent organic group containing a carbon atom, and each Y independently represents a hydrolyzable group] can be used.
[0221] <Primer layer for release> A detachment primer composition containing a siloxane-modified polyethyleneimine compound or the above-mentioned polybutadiene compound, having a solids mass % in the detachment primer composition shown in Table 18 below, was applied and dried using a gravure printing machine under the following conditions. The application amount of the detachment primer composition for each example in the table is the amount of solids in the coating layer per unit area. The solids concentration of the detachment primer composition is a concentration such that, when made into a coating layer, the siloxane-modified polyethyleneimine compound or the above-mentioned polybutadiene compound is present in the coating layer. (Removal primer composition application conditions) Coating machine: Gravure printing machine Coating speed: 100m / min Plate: Helio 175 line / inch (130°) solid plate (wet coating amount 6 g / m 2 degree) Drying temperature: 70℃ When printing with a gravure printer, the solid mass % of the release primer is diluted as shown below, and when printing with a gravure printer under the container conditions, the following application amount (g / m 2 ) Siloxane-modified polyethyleneimine compound: Trimethoxysilylpropyl-modified (polyethyleneimine) (trade name: SSP-060, Gelest), molecular weight 1,500-1,800, amine value 10 mmol / g, amine value measured by acid titration in a non-aqueous system, amine ratio measured by NMR (13C).
[0222] [Table 18]
[0223] Examples and comparative examples of printing formats in which the detachment primer composition containing the siloxane-modified polyethyleneimine compound of the present invention or the polybutadiene compound described above can be used will be described below in the order of reverse printing, front printing, shrink printing, and printing on the paper substrate side of laminated paper in which an adhesive is applied to a substrate film and the paper substrate is bonded to it. The printing format in which the primer composition for detachment described above that does not contain a siloxane-modified polyethyleneimine compound or the above polybutadiene compound is used, for reverse printing, front printing, shrink printing, on a base film, applying an adhesive, and printing on the paper base material side of a laminated paper obtained by bonding a paper base material, the same parts as in the examples and comparative examples are omitted.
[0224] <Examples and Comparative Examples of Reverse Printing Using a Siloxane-Modified Polyethyleneimine Compound> (Dry Lamination) ·Lamination Structure 1 : P-2161#25 / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / Adhesive (Takelac A-969V / Takelac A-5 Solids Content 30%) / VMC PP ·Lamination Structure 2 : Transparent Vapor-Deposited PET or Transparent Vapor-Deposited NY / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / Adhesive (Takelac A-515 / Takelac A-50, Solids Content 30 Mass%) Solids Content 30%) / RXC-22#60 (Extrusion Lamination) ·Lamination Structure 3 : PET or NY or Transparent Vapor-Deposited PET or Transparent Vapor-Deposited NY / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / AC Agent (Takelac A-3210 / Takelac A-3072, Solids Content 7 Mass%) / Melt Polyethylene ·Lamination Structure 4 : OPP / Siloxane-Modified Polyethyleneimine Compound / Each Reverse Printing Ink Composition / AC Agent (Epomin P-1000, Solids Content 0.7 Mass%) / Melt Polyethylene
[0225] <Deinking (Evaluation of Ink Detachment Property)> Deinking (evaluation of ink detachment property) was carried out as follows. 1.5 g of each of the above printed materials sufficiently dried after printing was shredded into small pieces of about MD15 mm × TD25 mm to obtain samples for the ink detachment property test. (Preparation of a Detachment Liquid Composed of an Aqueous Alkaline Solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid consisting of an alkaline aqueous solution. (Preheating of the desorption solution consisting of an alkaline aqueous solution) 100 g of the release solution consisting of an alkaline aqueous solution was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (detachment) After each release solution reached 70°C, the ink release test samples were placed in the respective alkaline aqueous solution release solutions, and the alkaline aqueous solution release solutions were stirred for 30 minutes using a 25mm diameter stainless steel stirring blade. After stirring, the HDPE (high-density polyethylene) container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solutions and the various film pieces were separated using a stainless steel mesh with approximately 2mm openings. (rinse) After removal, the various films were transferred to a 200cc HDPE container and 100g of water was added. The mixture was stirred for 5 minutes using a stainless steel stirring blade with a blade diameter of 25mm. After leaving the mixture to stand for 5 minutes, the various film pieces were separated from the water using a stainless steel mesh. After drying the various film pieces, the releasability of the ink from the various films was visually evaluated. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces. The laminate structures 1 to 4 all showed similar results as shown in Table 19. In addition, the polybutadiene compound was applied at a coating amount of 0.12 g / m 2 , which is the coating amount of the solid content of the polyethyleneimine compound in Table 19. 2 , 0.18g / m 2 In addition, the solids coating amount is 0.02 g / m 2 , 0.36g / m 2 The results of these four cases were the same as those in Table 19.
[0226]
Table 19
[0227] <Examples of surface printing using a C. siloxane-modified polyethyleneimine compound> Evaluation was carried out in the same manner as in the example of surface printing without using the above silane coupling agent, except that the primer for release was changed to the above silane coupling-modified polyethyleneimine-containing primer for release. For the surface printing ink compositions 1 to 8, the same results were obtained. The results for the surface printing ink composition 1 are shown in Table 20 below. Also, the above polybutadiene-based compound was used at solid content application amounts of 0.12 g / m 2 and 0.18 g / m 2 In addition, examples were also carried out where the solid content application amounts were 0.02 g / m 2 and 0.36 g / m 2 The results for these four cases were the same as those in Table 20.
[0228]
Table 20
[0229] <Examples of shrink printing using a C. siloxane-modified polyethyleneimine compound> Evaluation was carried out in the same manner as in the example of shrink printing without using the above silane coupling agent, except that the primer for release was changed to the above silane coupling-modified polyethyleneimine-containing primer for release. For the shrink packaging printing ink compositions 1 and 2, the same results were obtained. The results for the shrink packaging printing ink compositions 1 and 2 are shown in Table 21 below. Also, the above polybutadiene-based compound was used at solid content application amounts of 0.12 g / m 2 and 0.18 g / m 2In addition, examples were also carried out where the coating amount of the solid content was applied in two ways, 0.02 g / m 2 and 0.36 g / m 2 . The results of these four cases were the same as those in Table 21.
[0230]
Table 21
[0231] <Examples of Printing on the Paper Substrate Side of Laminated Paper Using a C. Siloxane-Modified Polyethyleneimine Compound> The desorption primer was evaluated in the same manner as in the example of printing on the paper substrate of laminated paper that does not use the above silane coupling agent, except that it was changed to the above siloxane-modified polyethyleneimine-containing desorption primer. The results are described in Table 22. In addition, the above polybutadiene-based compound was applied in two ways with a solid content coating amount of 0.12 g / m 2 and 0.18 g / m 2 , and in addition, examples were also carried out where the coating amount of the solid content was applied in two ways, 0.02 g / m 2 and 0.36 g / m 2 . The results of these four cases were the same as those in Table 22.
[0232]
Table 22
[0233] <Examples and Comparative Examples of Surface Printing Using a D. Polyethyleneimine Compound and a Commercially Available Gravure Printing Ink Composition> (Printing Ink Composition) XGS-922 N Blue 800 RE 2 (Sakata Inx Co., Ltd.) XGS 6116 Matte Medium R (Sakata Inx Co., Ltd.) (Resin Substrate) RXC-22#60: Unstretched Polypropylene Film (Mitsui Chemicals Toagosei Co., Ltd.) TUX-HC#50: Linear low-density polyethylene film, thickness 25 μm (Mitsui Chemicals Tocello Co., Ltd.) Siloxane-modified polyethyleneimine compound: Trimethoxysilylpropyl-modified (polyethyleneimine) (trade name: SSP-060, Gelest), molecular weight 1,500-1,800, amine value 10 mmol / g, amine value measured by acid titration in a non-aqueous system, amine ratio measured by NMR (13C).
[0234] (Production of printed matter) Two types of resin substrates, RXC-22#60 and TUX-HC#50, were prepared. Each polyethyleneimine listed in Table 1 above was diluted as shown in Table 2 above to form a release primer composition, which was then applied to one side of each of these two types of resin substrates using a gravure printing machine in the coating amount shown in Table 23 below, followed by drying. In examples where a silane coupling agent was used in combination, the release primer composition was prepared by using equal amounts of the polyethyleneimine compound and the silane coupling agent. Thereafter, XGS-922 N Indigo 800 RE-2 or XGS-6116 Matte Medium R was offset printed on each release primer composition and dried to obtain a print.
[0235] <Printing layer peeling test method> After printing, 1.5 g of each of the above printed materials was thoroughly dried and then shredded into small pieces of approximately 15 mm MD x 25 mm TD to obtain samples for the print layer peeling test. (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0236] (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release solution 1 (water) or for 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and the resin substrate film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces. Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces.
[0237] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each printed product obtained in the production of the printed product and then quickly peeled off. (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0238] <Evaluation of retort suitability (tape adhesion)> Under retort processing conditions, it was heated at 120°C for 30 minutes. After cooling to 25°C, a cellophane tape was attached to the printed surface of each printed matter, and the adhesiveness was evaluated according to the following evaluation criteria based on the degree of peeling of the printed layer when this was rapidly peeled off. (Evaluation Criteria) ○: No dropout of the ink composition of the printed layer. ×: There is dropout of the ink composition of the printed layer.
[0239] <Evaluation of Retort Suitability (Flexibility)> Under retort processing conditions, it was heated at 120°C for 30 minutes. After cooling to 25°C, each printed matter was strongly kneaded by hand for 5 minutes.
[0240] [Table 23]
[0241] As shown in the results of Table 23 above, when the primer composition of the present invention is used, the printed layer can be detached with an alkaline aqueous solution. Also, the retort suitability of the printed layer was sufficiently high.
[0242] <Examples and Comparative Examples of Surface Printing with a Commercially Available UV-Curable Inkjet Printing Ink Composition Using a Polyethyleneimine Compound or a Polybutadiene-Based Compound> (Printing Ink Composition) BSR06 (Sakata Inx Co., Ltd.) (Resin Substrate) RXC-22#60: Unstretched Propylene Film (Mitsui Chemicals Toatsu Chemicals, Inc.) TUX-HC#50: Linear Low-Density Polyethylene Film, Thickness 25 μm (Mitsui Chemicals Toatsu Chemicals, Inc.) · Siloxane-Modified Polyethyleneimine Compound: Trimethoxysilylpropyl-Modified (Polyethyleneimine) (Trade Name: SSP-060, Gelest Inc.), Molecular Weight 1,500 - 1,800, Amine Value 10 mmol / g, Amine Value Measured by Acid Titration in a Non-Aqueous System, Amine Ratio Measured by NMR (13C).) Polybutadiene compound (trade name: Titabond T-180E, (solid content concentration 10% by mass), Nippon Soda Co., Ltd.)
[0243] (Production of printed matter) Two types of resin substrates, RXC-22#60 and TUX-HC#50, were prepared. Each polyethyleneimine listed in Table 1 above was diluted to the amount listed in Table 2 above, and each release primer composition was applied to one side of each of these two types of resin substrates using a gravure printing machine in the coating amount listed in Table 24 below, followed by drying. Thereafter, BSR06 was inkjet printed onto each release primer composition, and then fully cured by sufficient irradiation with ultraviolet (UV) rays to obtain a printed product.
[0244] <Printing layer peeling test method> 1.5 g of each of the printed materials obtained by printing was shredded into small pieces of approximately 15 mm MD×25 mm TD to obtain samples for the print layer peeling test. (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0245] (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release solution 1 (water) or for 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and the resin substrate film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces. Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces.
[0246] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each printed product obtained in the production of the printed product and then quickly peeled off. (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film. Although different ink compositions were printed on each resin substrate, the results shown in the table below were the same.
[0247] [Table 24]
[0248] As shown in the results of Table 24 above, when the primer composition of the present invention is used, the printing layer can be peeled off with an alkaline aqueous solution. In Table 24, instead of applying each polyethyleneimine-based compound so that the coating amount of the solid content is 0.1 g / m 2 、0.02 g / m 2 、0.18 g / m 2 、0.36 g / m 2 , examples were also carried out in which the above polybutadiene-based compound was applied in four ways so that the coating amount of the solid content was 0.1 g / m 2 、0.02 g / m 2 、0.18 g / m 2 、0.36 g / m 2 . The results were the same as those when SP-018, P-1000, and P-3000 were adopted in each table.
[0249] <Examples and Comparative Examples of Surface Printing Using a Commercially Available Solvent-based Inkjet Printing Ink Composition Using a Polyethyleneimine Compound or a Polybutadiene-based Compound> (Printing Ink Composition) SS51C (Sakata Inks Co., Ltd.) (Resin Substrate) RXC-22#60: Unstretched Polypropylene Film (Mitsui Chemicals Toagosei Co., Ltd.) TUX-HC#50: Linear Low-density Polyethylene Film, Thickness 25 μm (Mitsui Chemicals Toagosei Co., Ltd.) · Siloxane-modified Polyethyleneimine Compound: Trimethoxysilylpropyl-modified (Polyethyleneimine) (Trade Name: SSP-060, Gelest), Molecular Weight 1,500 - 1,800, Amine Value 10 mmol / g, Amine Value Measured by Acid Titration in a Non-aqueous System, Amine Ratio Measured by NMR (13C).) Polybutadiene-based Compound (Trade Name: Titabond T-180E, (Solid Content Concentration 10% by Mass), Nippon Soda Co., Ltd.)
[0250] (Production of Printed Matter) Two types of resin substrates, RXC-22#60 and TUX-HC#50, were prepared. Each polyethyleneimine listed in Table 1 above was diluted as shown in Table 2 above, and each release primer composition was applied to one side of each of these two types of resin substrates using a gravure printing machine in the coating amount shown in Table 25 below, followed by drying. Thereafter, SS51C was ink-jet printed onto each release primer composition, and heated to completely dry, to obtain a printed product.
[0251] <Printing layer peeling test method> 1.5 g of each of the printed materials obtained by printing was shredded into small pieces of approximately 15 mm MD×25 mm TD to obtain samples for the print layer peeling test. (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0252] (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release solution 1 (water) or for 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and the resin substrate film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces. Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces.
[0253] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each printed product obtained in the production of the printed product and then quickly peeled off. (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film. Although different ink compositions were printed on each resin substrate, the results shown in the table below were the same.
[0254] [Table 25]
[0255] As shown in the results in Table 25 above, when the primer composition of the present invention is used, the printed layer can be removed with an alkaline aqueous solution. In Table 25, each polyethyleneimine compound was applied at a solids coating amount of 0.1 g / m 2 , 0.02g / m 2 , 0.18g / m 2 , 0.36g / m 2 Instead of applying the polybutadiene compound so that the solid content was 0.1 g / m 2 , 0.02g / m 2 , 0.18g / m2 、Applied at 0.36 g / m 2 Examples were also carried out in four ways. The results were the same as those when SP-018, P-1000, and P-3000 were adopted in each table.
[0256] <Examples and Comparative Examples of Surface Printing Using a G. Polyethyleneimine Compound and a Commercially Available EB (Electron Beam) Curing Type Offset Printing Ink Composition> (Printing Ink Composition and EB Curing Type Varnish Composition) EB Offset Printing Ink Composition PB15:3 (22.7 parts by mass), polyester acrylate oligomer (CN704 (Sartomer)) (40.0 parts by mass), methylhydroquinone (0.1 part by mass), 6EO modified TMPTA (6EO modified trimethylolpropane triacrylate) (36.2 parts by mass), dimethyl silicone oil (TSF-451-5M (Momentive)) (1.0 part by mass) Bellflower R Blue 800MK (Sakata Inks) EB Curing Type Varnish Composition Rosin modified maleic acid resin (Harima M-453 (Harima Chemicals)) (50.0 parts by mass), trimethylolpropane triacrylate (49.5 parts by mass), dimethyl silicone oil (KF-96H-1 (Shin-Etsu Silicone)) (0.5 part by mass) (Resin Substrate) RXC-22#60: Unstretched propylene film (Mitsui Chemicals Tohcello) TUX-HC#50: Linear low density polyethylene film, thickness 25 μm (Mitsui Chemicals Tohcello) · Siloxane modified polyethyleneimine compound: Trimethoxysilylpropyl modified (polyethyleneimine) (trade name: SSP-060, Gelest), molecular weight 1,500 - 1,800, amine value 10 mmol / g, amine value measured by acid titration in non-aqueous system, amine ratio measured by NMR (13C).)
[0257] (Production of Printed Matter) Two types of resin substrates, RXC-22#60 and TUX-HC#50, were prepared. Each polyethyleneimine listed in Table 1 above was diluted to the amount listed in Table 2 above, and each release primer composition was applied to one side of each of these two types of resin substrates using a gravure printing machine in the coating amount listed in Table 27 below, followed by drying. Then, an EB offset printing ink composition was offset printed on each release primer composition and cured to obtain a printed product. Also, Bellflora R Indigo 800MK was gravure printed on each release primer composition to form a printed layer, and an EB-curable varnish composition was further applied on top of that and cured to obtain a printed product.
[0258] <Printing layer peeling test method> After printing, 1.5 g of each of the above printed materials was thoroughly dried and then shredded into small pieces of approximately 15 mm MD x 25 mm TD to obtain samples for the print layer peeling test. (Preparation of Water-Based Elution Solution 1) Water-only desorption solution 1 (Preparation of release solution 2 consisting of alkaline aqueous solution) 2.0 parts by mass of sodium hydroxide was added to 98.0 parts by mass of water, and the mixture was stirred and dissolved to obtain a release liquid 2 made of an alkaline aqueous solution. (Preheating of desorption solution 1) 100 g of the release solution 1 consisting of water was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C. (Preheating of desorption solution 2) 100 g of the release solution 2, which was an alkaline aqueous solution, was placed in each 200 cc HDPE (high density polyethylene) container, and heated in a hot water bath until the liquid temperature reached 70°C.
[0259] (detachment) After the temperature of the release solution reached 70°C, the print layer peeling test sample was placed into each release solution and stirred for 60 minutes using a stainless steel stirring blade with a blade diameter of 25 mm for release solution 1 (water) or for 30 minutes for release solution 2 (an alkaline aqueous solution). After stirring, the HDPE container was removed from the hot water bath and allowed to stand at room temperature for 5 minutes. The release solution and the resin substrate film pieces were separated using a stainless steel mesh with mesh openings of approximately 2 mm. Desorption (alkali) conditions: 70°C, 30 minutes of stirring in 2% sodium hydroxide solution (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces. Desorption (hot water) conditions: 70°C hot water, stirring for 60 minutes (Evaluation criteria) ○: The ink film was completely peeled off from the resin substrate film as film pieces. ×: The ink film did not peel off from the resin substrate film as film pieces.
[0260] <Evaluation of adhesion to substrate> Adhesion was evaluated according to the following criteria based on the degree to which the printed film peeled off when cellophane tape was applied to the printed surface of each printed product obtained in the production of the printed product and then quickly peeled off. (Evaluation criteria) ◯: Peeling from the film was less than 5% of the area of the printed coating. △: 5% or more but less than 30% of the area of the printed coating peeled off from the film. ×: 30% or more of the area of the printed coating peeled off from the film.
[0261] <Evaluation of retort suitability (tape adhesion)> The prints were heated to 121°C for 5 minutes under retort processing conditions. After allowing them to cool to 25°C, cellophane tape was applied to the printed surface of each print, and the tape was quickly peeled off to evaluate the degree to which the printed layer peeled off, according to the following evaluation criteria. (Evaluation criteria) ◯: No ink composition was removed from the printed layer. ×: The ink composition of the printed layer fell off.
[0262] <Evaluation of retort suitability (kneadability)> Under retort processing conditions, the printed materials were heated at 121°C for 5 minutes. After cooling to 25°C, each printed material was rubbed vigorously by hand for 5 minutes, and the degree of peeling of the printed layer was used to evaluate adhesion according to the following evaluation criteria. (Evaluation criteria) ◯: No ink composition was removed from the printed layer. ×: The ink composition of the printed layer fell off. Although different ink compositions were printed on each resin substrate, the results shown in the table below were the same.
[0263] [Table 26]
[0264] As shown in the results in Table 26 above, when the primer composition of the present invention was used, the printed layer could be removed with an alkaline aqueous solution. In addition, the retort suitability of the printed layer was sufficiently high. As shown in the results of Tables 19 to 26 above, when the primer composition of the present invention was used, the printed layer could be removed with an alkaline aqueous solution, and the laminate strength of the printed layer was sufficiently strong.
Claims
1. A printed matter formed in the following order: a resin substrate, a detachable primer layer, and a printed layer, wherein the printed layer is formed from an inkjet ink composition and / or an offset ink composition, and the detachable primer composition for forming the detachable primer layer contains a polyethyleneimine-based compound having an amine value of 5.0 to 25.0 mmol / g and / or a polybutadiene-based compound.
2. A printed matter formed in the following order: a resin substrate, a detachable primer layer, an adhesive layer, a paper substrate layer, and a printed layer, wherein the printed layer is formed from an inkjet ink composition or an offset ink composition, and the detachable primer composition for forming the detachable primer layer contains a polyethyleneimine-based compound having an amine value of 5.0 to 25.0 mmol / g and / or a polybutadiene-based compound.
3. The printed matter according to claim 1 or 2, wherein the detachment primer composition containing a polyethyleneimine-based compound having an amine value of 5.0 to 25.0 mmol / g contains any one or more of the following A to C: A. Polyethyleneimine Compounds B. A mixture containing a polyethyleneimine compound and a glycidyl group-containing silane coupling agent and / or an isocyanate group-containing silane coupling agent C. Siloxane-modified polyethyleneimine compound
4. 4. The printed matter according to claim 3, wherein the number average molecular weight of the polyethyleneimine compound or the siloxane-modified polyethyleneimine compound is 1,000 to 200,000.
5. 4. The printed matter according to claim 3, wherein the polyethyleneimine compound and the siloxane-modified polyethyleneimine compound have a mass average molecular weight of 4,000 to 800,000.
6. 3. The printed matter according to claim 1 or 2, wherein the polybutadiene-based compound-containing detachment primer composition contains a hydroxyl group-containing polybutadiene compound and / or a carboxyl group-containing polybutadiene compound.
7. 3. The printed matter according to claim 1 or 2, further comprising a layer of a varnish composition formed on the printed layer.
Citation Information
Patent Citations
JP1988088131A
Resin for printing ink
JP1993097959A
Recycled base material manufacturing method
JP2020175620A
Organic solvent-based printing ink with releasability, printed matter and laminate
JP6631964B1
Releasable laminating adhesive from composite film, laminate, and method for recycling sheet-like substrate
JP6642688B1